Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2021)
A dataset containing 369952989 species occurrences available in GBIF matching the query: (Query is too complex. Can be viewed on the landing page) The dataset includes 369952989 records from 15053 constituent datasets: 50 records from Données 2016 Pélobate brun Comité Départemental de Protection de la Nature et de l'Environnement. 27 records from Revision of the genus Parvimysis (Mysida, Mysidae) with descriptions of five new species from coastal waters of the Caribbean. 342 records from The genus Mecodema Blanchard 1853 (Coleoptera: Carabidae: Broscini) from the North Island, New Zealand. 204 records from COA Bird Collection (Arctos). 84 records from Great British Bee Count 2016 - Stage 2 (records verified from photo). 831 records from Bryophyte specimens of The Nagoya University Museum. 1 records from The fossil record of the family Benthopectinidae (Echinodermata, Asteroidea), a reappraisal. 6 records from Chronicle of Nature - Phenology of Insects of National Park Bashkirija. 5283 records from University of Guam Insect Collection. 25 records from Dermaptera of Iran with description of Euborellia angustata sp. nov.. 9 records from Monocotiledóneas del cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO 2017. 30 records from Artenvielfalt des "Grünen Klassenzimmers". 562 records from Zoocenosis of the mole burrows in the forest zone of Western Siberia. 338 records from Museu de Ciències Naturals de Barcelona: BGJBB. 4 records from Taxonomy of ant species (Hymenoptera: Formicidae) collected by pitfall traps from Sinai and Delta region, Egypt.. 1642 records from Inventario florístico y entomofaunístico en tres objetos de conservación ecosistémicos en las zonas núcleo de las reservas estatales de Balam-kú y Balam-kin, Campeche (Plantas). 26 records from Inventaire biodiversité du site Pierre Fabre d'Aignan. 591 records from MCP-Aves - Coleção de Aves. 121 records from Bird specimens of Saitama Museum of Natural History. 100 records from orthopteracollections-nhmj-ioj. 2 records from Carnivores of Syria. 1440 records from Collections of Bioclass, school #179, Moscow. 33 records from Microbial community structure and dynamics in the oxygen minimum zone of the Northeast subarctic Pacific Ocean. 98 records from Mycology collection, Norwegian Forest and Landscape Institute. 30 records from New Records of ground beetles for Colombia (Coleoptera: Carabidae). 54 records from flower availability 2008 Alb-korrigiert. 259 records from Inventario de flora, avifauna, mamíferos, mariposas y peces realizado en el sector de Puerto Abeja y durante la expedición científica en la ventana Mesay en el sector sur del Parque Nacional Natural Serranía de Chiribiquete. 1 records from Revision of the Australian Union-Jack wolf spiders, genus Tasmanicosa (Araneae, Lycosidae, Lycosinae). 65822 records from Digitalización y sistematización de las colecciones biológicas del INECOL (Herbario). 480 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2015. 173 records from UWIZM Anoles. 769 records from Pat Livermore's Fungus Records 1976 - 2000. 6 records from Riedkanal Bötzingen. 4 records from Aves marinas del atolón Albuquerque durante la Expedición Seaflower 2018 - Proyecto Colombia BIO. 89 records from Herbario del Museo de Historia Natural C.J. Marinkelle. 43 records from Données du/de la naturaliste Williamson Thomas provenant de la base de donnée du SINP Île-de-France CETTIA. 13 records from Seven new species and additional records of Palaearctic Leptusa, primarily from Yunnan, China (Coleoptera: Staphylinidae: Aleocharinae). 75 records from Revision Of The Australian Coccinellidae (Coleoptera). Genus Novius Mulsant Of Tribe Noviini. 274 records from Diatomeas (Bacillariophyceae) y dinoflageladas (Dinophyceae) planctónicas más frecuentes en el Golfo de California. 1214212 records from Dragonfly records from the British Dragonfly Society Recording Scheme. 1 records from eDNA_Subseafloor. 22 records from A revision of the genus Disparalona (Cladocera, Chydorinae) in South America. 1460 records from Captive Primate Specimens of Japan Monkey Centre. 61 records from Inventario de vertebrados nativos en las islas Guadalupe, San Benito, Natividad, Asunción, San Roque, Isabel, Marietas, Socorro, Banco Chinchorro y Arrecife Alacranes (Crustáceos). 4925 records from Invasive Plant Atlas of the MidSouth (IPAMS). 1254 records from Biodiversity of the Desna river valley and its tributaries. 779 records from Códigos de barras de la vida en peces y zooplancton de México. 8005 records from Herbarium Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 13 records from Rhaphium (Diptera: Dolichopodidae: Rhaphiinae) from China with six new species. 667 records from Antarctic Krill occurrence data from Discovery expeditions. 126 records from Plant species from the sacred and community forests of Mono departement. 12 records from Updated checklist of Balearic leaf beetles (Coleoptera: Chrysomelidae). 38 records from Colección Ornitológica-Museo de Historia Natural Unillanos. 109 records from Collection des mammifères d'Auvergne. 3 records from Report on a collection of dragonflies (Odonata) from the Andaman Islands.. 12 records from Pseudotibiozus Demange, 1970 - millipedes of the Eastern Arc Mountains, Tanzania (Diplopoda, Spirostreptida, Spirostreptidae). 5999 records from Arbeitsgemeinschaft Heuschrecken Österreichs. 279 records from Australian Institute of Marine Science (AIMS) - Lizard Island Reef Biodiversity Expedition, Queensland, Australia (2008 - 2009). 26 records from Soil metagenome from healthy and unhealthy agricultural soil. 48 records from Morphologische Daten von Natrix. 3 records from A new species of Ahaetulla Link, 1807 (Serpentes: Colubridae: Ahaetullinae) from India. 4 records from New state and island records of Coccinellidae (Coleoptera) in Hawai‘i, USA. 5 records from Collection botanique Lamy de la Chapelle E. (BOUM). 2815 records from Brown University Herbarium. 19 records from Données du/de la naturaliste Le baron Gaetan provenant de la base de donnée du SINP Île-de-France CETTIA. 121 records from Caracterización biológica de la ventana de biodiversidad Montes de María, Municipio de Colosó, Sucre, Colombia. 12 records from BIRDRACE accipiter hardcore birding. 2085 records from Inventaire de la flore des Pyrénées-Atlantiques 2017 - Littoral. 34 records from Occurrence of mammalia relicts at site Spitzbubenhöhle. 74 records from The millipede genus Glomeris Latreille, 1802 (Diplopoda, Glomerida, Glomeridae) in North Africa. 882 records from LISU Herbario Angola. 1132 records from nhmc_ob_2019. 384 records from CNAC/Coleccion Nacional de Acaros. 2 records from Intraspecific variation in adult Uvitellina iraquensis Dronen, Ali & Al-Amura, 2013 (Cyclocoelidae: Haematotrephinae) from two collection sites of white-tailed lapwing, Vanellus leucurus (Lichtenstein) (Charadriiformes: Charadriidae), in Iraq. 2 records from RNF - Données de la Réserve Naturelle du Marais de Lavours. 783 records from Tropical epiphyte diversity under human impact ? Comparing primary forests, secondary forests, and forest fragments in Ecuador - Otonga. 5 records from Description of two new species of the genus Automate De Man, 1888 (Crustacea: Decapoda: Caridea) from the South China Sea. 292 records from Inventaire des espèces végétales productives dans les Systèmes Agro-forestiers aux alentours de la Forêt classée de Ziama en Guinée Forestière (BID-AF2015-0066-REG). 4 records from A new cave-dwelling Gekko (Gekko) from Lopburi Province, central Thailand (Squamata, Gekkonidae). 11 records from BioAcoustica: Wildlife Sounds Database. 8 records from The millipede genus Tylopus Jeekel, 1968 (Diplopoda, Polydesmida, Paradoxosomatidae), with a key and descriptions of eight new species from Indochina. 206 records from INVESTIGATING THE MICROBIAL EUKARYOTIC COMMUNITIES IN THE SURFACE WATERS OF THE ARAFURA SEA AND CORAL SEA. 252 records from TransForest - vegetation, lichen and fungi data 2016. 55 records from artsprosjektet_51-14_ophiostomatoid_fungi. 8 records from Registros de la vegetación presente en la Cienaga de Beté, Municipio del Medio Atrato, Chocó - 2018. 6 records from CEFS_16S_ITS. 7159 records from Biowide Species data. 51 records from Pollen analysis of sediment profile TR0 from Truennensee. 317 records from Macrobenthos Chukchi Sea, 1986. 8 records from Condamine Alliance. 3 records from A new species and new record of the leafhopper genus Balclutha (Hemiptera: Cicadellidae: Deltocephalinae) from China with key to species. 34 records from Inventory of natural and agroforestry stands characterized by Xylopia aethiopica (Dunal) A. Rich. (south-Benin). 70 records from Inventario taxonómico de los hongos conidales saprobios del parque Yumka' en Villahermosa, Tabasco. 91 records from Schanzenanlage Bergham. 36 records from Reptiles presentes en la colección herpetológica SINCHI de la expedición al Río Apaporis - Proyecto Colombia BIO. 49 records from Herbarium of the Institute of the problems of Northern development (TMN). 144 records from Station de Biologie des Laurentides de l'Université de Montréal - Collection Ornithologique. 149 records from Legume Collections of the Plant Genetic Resources Research Institute (CSIR-PGRRI),Ghana. 38 records from Comparative study in validity of three regions of 18S-rRNA for eukaryote amplicon sequence analyses. 10 records from Contributions to the study of the grasshopper (Orthoptera: Acrididae Gomphocerinae) courtship songs from Kazakhstan and adjacent territories. 6652 records from Crustacean specimens of Kitakyushu Museum of Natural History & Human History. 4 records from Faunal assemblage of sediment core TR149-31. 13 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/587-16. 3 records from The interstitial subsoil fauna of the lower beach level at Sarso Beach, Red Sea (Table 4). 599 records from Distribución histórica, prospección actual y áreas potenciales para reintroducir lobo mexicano (Canis lupus baileyi) en Durango, sur de la Sierra Madre Occidental, México. 30 records from AVJNF: Søholt Storskov, amphibian survey. 10 records from Naturtag. 9 records from données espèces - Expertise IPE 63. 357 records from Herbier Louis-Marie (QFA) - Collection de lichens. 117 records from Amphibian Specimens of the Yamagata Prefectural Museum. 10 records from On the Staphylinidae of the Greek island Samothraki (Insecta Coleoptera). 33178 records from Oiseaux nicheurs de France métropolitaine 2009-2012 - Nidification probable. 64 records from Marsabit Ecosystem Inventory Surveys 2014. 5 records from New host-plants records of Afrotropical Gelechiidae (Lepidoptera), with description of three new species. 74350 records from Plant. 3 records from A new Rhopalomeris species (Diplopoda: Glomerida: Glomeridae), and notes on the phylogenetic relationships between glomeridans in Vietnam. 3250 records from Characterizing bumble bee (Bombus) communities in the United States and assessing a conservation monitoring method. 1431 records from Apoyo a las colecciones biológicas de la Facultad de Ciencias de la UNAM: Fase 1 (Abejas). 123 records from Taxonomy of widespread Neotropical species of Podisus Herrich-Schäffer (Hemiptera: Pentatomidae: Asopinae): redescription of P. distinctus (Stål, 1860) and revalidation of P. fuscescens (Dallas, 1851). 55 records from Colección de Vertebrados (naturalizados y en fluido) del Departamento de Zoología de la Facultad de Biología de la Universidad de Sevilla. 406 records from Plecoptera. 123 records from Freshwater crustaceans in Antarctic and sub-Antarctic lakes. 3 records from Données naturalistes d'Arnaud LE NEVÉ. 708 records from Swan Coastal Plain Survey. 151 records from University of Amsterdam (NL) - Páramo Vegetation Research, National Natural Park El Cocuy, Colombia. 5 records from Redescription and phylogenetic analysis of the type species of the giant pill-millipede genus Sphaeropoeus Brandt, 1833 (Diplopoda, Sphaerotheriida, Zephroniidae). 82 records from Taxonomic And Distributional Notes On Perlesta Teaysia, P. Golconda, And P. Shawnee (Plecoptera: Perlidae). 24 records from New findings on the Neotropical species Hermetia goncalvensi Albuquerque, 1955 (Diptera: Stratiomyidae): redescription, puparium, and geographical records. 478 records from Bees in the UVM Zadock Thompson Zoological Collection. 4 records from NZCS Brownsberg Nature Park Monitoring. 2 records from Analyses of the recent components of sediment core PS1219-1. 8 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/088-4. 7 records from Hessen-GEO-Tag am Schlossberg von Homberg/Efze. 4950 records from Insect collection of Biodiversity Center of Japan, Ministry of the Environment. 20247 records from North East Scotland Terrestrial Mammals 1900-2017 (excluding squirrels, wild cats and marine mammals). 11 records from EDP Foz-Tua: Riparian Birds (point counts) Ecological Monitoring Program [2011]. 1 records from Spatial variation of bacterioplankton in south Atlantic Bight. 38 records from Steinbruch Mainz-Weisenau, 3. Jahr. 24 records from NZCS Nassau Mountain Expeditions 2005/2006/2010/2014. 1821 records from Museu Paraense Emílio Goeldi - Carcinológica Collection. 809 records from Inventario florístico de la Sierra de Huautla, Morelos. 22 records from Inventario de sanguijuelas (Annelida: Clitellata Hirudinea) de México, con énfasis en las especies del centro de México. 85 records from Pollen profile V and Ausfluss at Krumbach, Germany. 2 records from Description of a new species of Cosmocerca Diesing, 1861 (Nematoda Cosmocercidae) in Hoplobatrachus crassus (Jerdon, 1853) (Anura: Dicroglossidae from Asansol coal-field area, West Bengal, India. 13 records from BIRDRACE The early birds. 1609 records from Données odonates collectées par le CEN Aquitaine entre 1995 et 2015. 59563 records from University of Michigan Museum of Zoology, Division of Reptiles & Amphibians. 1065 records from RECORD Orthoptera Data. 25 records from DFO Pacific Outside South Hard Bottom Longline Surveys. 44 records from Bird species occurrences recorded from selected sites in mid Tana River Basin, Kenya. 256 records from (UTC) University of Tennessee Mammals Collection. 204 records from Données du naturaliste PROVOST romain provenant de la base de donnée du SINP Île-de-France CETTIA. 261 records from MBON POLE TO POLE: ROCKY SHORE BIODIVERSITY OF ARRAIAL DO CABO - BRAZIL. 7579 records from Birds Specimens. 112 records from Antarctic Pycnogonids II. 8166 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 24 records from Schulgelände Kranich-Gymnasium (Salzgitter). 165 records from Suivi de l'expansion du Frelon asiatique (Vespa velutina) : données espèces non cibles piégées. 107 records from Caracterización de Fauna del Banco de Hábitat del Bosque Seco Tropical Antioquia de Terrasos. 574 records from Herpetofauna de la región marina prioritaria Corredor Puerto Madero, Chiapas, México. 1607 records from 2020_biodiversity_information_specimen. 116 records from Upper Silesian Museum, Bird Observations. 16 records from Fliegenhaupt Marksuhl. 59 records from Type specimens of invertebrate collection at University of Oulu Zoological Museum. 3779 records from DMNS Mammal Collection (Arctos). 792 records from Données naturalistes de Quentin ROME. 409 records from Back from the Brink vascular plant species abundance and distribution for Great Britain for the period 2002-2009. 1 records from A new species of the genus Pachytriton (Caudata: Salamandridae) from Hunan and Guangxi, southeastern China. 43 records from Occurrence of mammalia relicts at site Rejtek 1. 5 records from Morphological and molecular description of a new genus and species of black coral (Cnidaria: Anthozoa: Hexacorallia: Antipatharia: Antipathidae: Blastopathes) from Papua New Guinea. 84 records from SEWBReC Springtails and allies (South East Wales). 20 records from Four new species of Phrynus, Lamarck (Arachnida: Amblypygi) from Mexico. 6 records from Culicoides Latreille biting midges (Diptera: Ceratopogonidae) of the Dongzhaigang mangrove forest, Hainan Province, China. 689 records from Relative abundance of adult opstracoda shells of surface sediment samples from the Persian Gulf (Table 1b). 75 records from Insectos recolectados en trampas Malaise en el departamento de Santander - Proyecto Colombia Bio. 295 records from IBF Monitoring of Fungi. 130 records from Sagehen Creek Field Station (UC-Berkeley) - Birds. 11685 records from The Himalayan Uplands Plant database (HUP Version 1). 40 records from Artenvielfalt auf dem Schulgelände. 2 records from Suivi des aires marines protégées de Moorea - Invertébrés benthiques. 4 records from New and little known species of Lepechinella (Crustacea, Amphipoda, Lepechinellidae) and an allied new genus Lepesubchela from the North Atlantic. 4 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Especies observadas en Mercedes (Unterkofler, octubre 1999). 1898 records from MICA - Muskrat and coypu camera trap observations in Belgium, the Netherlands and Germany. 2 records from Analyses of the recent components of sediment core PS1277-1. 18 records from A new genus for the freshwater crab Potamonemus asylos Cumberlidgeı 1993 ı (Brachyura: Potamoidea: Potamonautidae) from Cameroonı Central Africaı with a key to the genera of the Potamonautinae. 9059 records from MEXU/Leguminosae. 18 records from The millipede family Polyxenidae (Diplopoda, Polyxenida) in the faunas of the Crimean Peninsula and Caucasus, with notes on other European Polyxenidae. 22 records from Waldstück Bremerhagen LK Bio Kl. 12. 1 records from Rediscovery of Lestes nigriceps Fraser, 1924 (Odonata: Lestidae) in eastern Cambodia. 11 records from Inventaire des mammifères du Parc de la Haute-Île (93). 5 records from Phase-contrast synchrotron microtomography reveals the internal morphology of a new fossil species of the Corticaria-sylvicola - group (Coleoptera: Latridiidae). 15 records from The genus Calodera Mannerheim in Canada (Insecta, Coleoptera, Staphylinidae, Aleocharinae). 39 records from Stomatopod Crustacea of the Austral and Gambier Islands, French Polynesia. 558 records from Studies in Hawaiian Diptera II: New Distributional Records for Endemic Scatella (Ephydridae). 7580 records from Insect specimens in the Museum of Nature and Human Activities, Hyogo Prefecture, Japan. 3 records from Invasive plants in Luronium natans habitats in Flanders, Belgium. 328 records from Estudio florístico de los bosques mesófilos de la Sierra Mazateca de Oaxaca, México. 58 records from Bannwald Burghauser Forst. 914 records from Bulletin du Muséum d'Histoire Naturelle [1895- ]. 14933 records from SEWBReC Bees, Wasps and Ants (South East Wales). 54 records from Coral Reef Evaluation and Monitoring Project Dry Tortugas 2007. 520 records from BenthosChukchiFN762_1976_Falk5. 3 records from New data on jumping spiders of Iran, with a new species of Salticus (Araneae: Salticidae). 29 records from Programme de valorisation des zones humides chassées - volet Amphibiens. 1357 records from National Museum of Natural Science. 729 records from A survey of the weevils of Ukraine (Coleoptera: Curculionoidea). 255 records from Caracterización de flora, edafofauna epígea, anfibios y aves del Complejo de Páramos Pisba, Boyacá. 41 records from Eupithecia gypsophilata, a new species in the graphata species group of the genus Eupithecia Curtis (Lepidoptera, Geometridae, Larentiinae). 1 records from Caracterización floristica del Alto del Buey, Bahia Solano - Chocó. 100 records from Fig. 4. Pollen record of profile SAO1 (Analyst: J. Hahne). 16 records from Taxonomic Accounts With Notes On Spatial Diversity And Relative Abundance Pattern Of Horseflies (Diptera: Tabanidae) From Sonamukhi Protected Forest Area Of West Bengal, India. 12 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-18. 6 records from Catalog of the Paramacronychiinae of China (Diptera: Sarcophagidae). 2 records from Global Ocean Sampling Expedition. 8 records from BIRDRACE Pfeifenten. 20 records from Données 2017 de l'Observatoire de la Biodiversité des Forêts. 7820 records from Port Phillip Bay Environmental Study Data 1992-1996 - benthic records. 1 records from Enneophyllus ecarina, a new species of scaphopod shell dwelling hermit crab (Crustacea: Decapoda: Anomura: Paguridae) from deep-sea off the Ryukyu Islands, southern Japan. 36 records from Marine metagenome ICM_JRV. 8 records from A new crab-associated amphipod of the genus Isaeopsis Barnard, 1916 (Amphipoda Senticaudata: Ischyroceridae) from southern Chile. 45 records from Données de la naturaliste Laurence Beauchamp. 36 records from Knechtweide (Kohlfurth). 624 records from Butterflie Specimens of Yamaguchi prefectural Yamaguchi Museum. 97 records from Ladybirds of Ireland. 67 records from Collections ichtyologiques et herpétologiques (BOUM). 140 records from MCP-Mamiferos - Coleção de Mamíferos. 1643 records from Données naturalistes de Bruno OGER. 373 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 26 records from Données du Syndicat de la Vallée de l'Orge Aval (SIVOA). 42 records from Meniscus Midges (Dixidae) of Ireland. 12 records from Description of a new species of Glassella Campos & Wicksten, 1997 from a coastal lagoon, SE Gulf of California (Crustacea, Decapoda, Pinnotheridae). 45 records from Expediciones en biodiversidad alrededor del Cacao en el marco del proyecto Colombia Bio. 1 records from A new deep-sea species of the caridean genus Bresilia Calman, 1896 (Crustacea: Decapoda: Bresiliidae) from Sagami Bay, central Japan. 11 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/591-11. 40 records from Alien Species in Poland - Animals. 32 records from Occurrence database of native plants and animals of south-central Chile. 4446 records from Pteridophyta collection of Museum of Natural and Environmental History, Shizuoka. 60 records from Données du/de la naturaliste Swoszowski Florie provenant de la base de donnée du SINP Île-de-France CETTIA. 20 records from Occurrence of mammalia relicts at site Pestera Bursucilor. 233 records from Swiss National Bat Databank: Regional Coordination Western Switzerland (CCO). 35 records from Natura 2000 Parc naturel régional de Lorraine. 4870 records from Données de l'AFB acquises selon le protocole de pêche complète à un ou plusieurs passages. 2227 records from Census of the species of Benin. Data mobilized in the framework of JRS Benin project and funded by JRS Biodiversity Foundation. 36 records from Arácnidos - Miriápodos de la expedición al Río Apaporis - Proyecto Colombia BIO. 11 records from On the Bennelongia nimala and B. triangulata lineages (Crustacea, Ostracoda) in Western Australia, with the description of six new species. 71 records from South American Leaf-Cutter Bees (Genus Megachile) Of The Subgenera Rhyssomegachile And Zonomegachile, With Two New Subgenera (Hymenoptera: Megachilidae). 1 records from Zambian Bat Collections Worldwide. 28 records from A new freshwater shrimp species of the genus Palaemon Weber, 1795 (Decapoda: Caridea: Palaemonidae) from northeastern Japan. 126 records from Pollen profile ADR353. 2740 records from Vascular plants of south-central China. 29 records from Entomological collection of the National Museum. 23599 records from Fichier communal des ongulés. 5 records from BIRDRACE Punkbirder Helgoland. 12 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/041-2. 1 records from Sächsische Schweiz (Pfaffenstein). 4 records from Campydoroides manautei gen. et sp. nov. from New Caledonia and a reappraisal of the suborder Campydorina (Nematoda). 22 records from Four new crane fly species of subgenus Tipula (Vestiplex) (Diptera, Tipulidae) from China. 93 records from Swedish Malaise Trap Project (SMTP) - Mycetophilidae, Keroplatidae. 85447 records from Field Museum of Natural History (Zoology) Amphibian and Reptile Collection. 8 records from More cautionary tales: family, generic and species synonymies of recently published taxa of ghost and mud shrimps (Decapoda: Axiidea and Gebiidea). 7 records from Two new species and two newly recorded species of the subgenus Empoasca Walsh from Korea (Hemiptera: Cicadellidae: Typhlocybinae). 833 records from Collection Vermes - ZMB. 1 records from Culture Collection of Algae. 1393 records from SIM-Fungal records compiled by Joan Montón. 13 records from BIRDRACE - The famous Grouse feat. The James. 45776 records from Western Australian Museum provider for OZCAM. 26 records from ABC_Event data recorded on a day trip to Mongolwe and Chikala Hills Forest Reserve, Machinga District. 836 records from Diversidad vegetal en un gradiente en la Sierra Madre Occidental: flora y vegetación de la Región de San Javier y Yécora, Sonora. 1 records from Parasitoides de Cochinilla. 5 records from Colección de mamíferos voladores y no voladores de la Universidad de Nariño. 21 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 7 records from Visual Plants (144.41.33.158) - Plants from the Kakamega Forest, Kenya; Helmut Dalitz. 48 records from Flora vascular y no vascular: expedición Cuenca Media del río Chicamocha - Proyecto Boyacá BIO UPTC. 4 records from Mumetopia interfeles sp. nov., a new species of Anthomyzidae (Diptera) occurring en masse in an urban grassy habitat in Chile: its taxonomy, phylogeny and biology. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 6339 records from VIES herbarium - Universidade Federal do Espírito Santo - Herbário Virtual REFLORA. 240014 records from Bryophyte data for Great Britain from the British Bryological Society held by BRC: Atlas 2014. 2 records from Baetis pentaphyllus sp. nov., a new species of mayfly (Ephemeroptera: Baetidae) from the Russian Far East. 43352 records from NRW Regional Data: South East Wales Non-sensitive species. 23 records from Aves de la expedición en el páramo El Valle, Boyacá - Proyecto Boyacá BIO. 1 records from A new high-altitude species of centipede from the Andes of Ecuador (Chilopoda, Geophilomorpha, Schendylidae). 86 records from Recursos hidrobiológicos de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 5 records from Three new country records from the genus Limnephilus Leach, 1815 (Trichoptera: Limnephilidae) from the Republic of Kosovo. 13783 records from CEPEC herbarium - Centro de Pesquisas do Cacau - Herbário Virtual REFLORA. 3 records from Diet, Tidal and Vertical Variations of Phytoplankton and Its Environment in Frobisher Bay, Canada, 1980 and 1981. 48 records from New genera for species of Jassa Leach (Crustacea: Amphipoda) and their relationship to a revised Ischyrocerini. 609 records from Inventaire de la flore du Grand Poitiers 2009. 11 records from Waldstück am Schullandheim Bad Bederkesa. 4 records from Occurrence of mammalia relicts at site Goyet Cave 3. 24 records from Anfibiofauna asociada a la quebrada Giginia, corregimiento de Doña Josefa, Municipio del Atrato - Chocó, 2019. 47 records from Aves de la expedición en el páramo de Bijagual, Boyacá - Proyecto Boyacá BIO. 249 records from M. Gollop Collection. 1016 records from Collembola of Karelia: multiscale analysis of spatial distribution in pine forests. 13029 records from Naturalis Biodiversity Center (NL) - Diptera. 5 records from Schulgarten der Gesamtschule Am Heidberg. 2 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-11. 23 records from New species of Condylostylus Bigot (Diptera: Dolichopodidae) from Comoros Madagascar, Tanzania and South Africa, with key to Afrotropical species. 287 records from Données du/de la naturaliste Lantz André provenant de la base de donnée du SINP Île-de-France CETTIA. 24 records from Schulhof Gymnasium Hürth Bonnstrasse. 157 records from Read between the lineata: A revision of the tattooed wasps, Zagrammosoma Ashmead (Hymenoptera: Eulophidae), with descriptions of eleven new species. 1 records from Berlese's Primitive Oribatid Mites. 7 records from Chapter 7: Linnaean Plant Names and their Types (part O). 17 records from Gewässer des Wartbergparks Stuttgart (bei der Ökostation der VHS Stuttgart). 5 records from Society Islands beach bum black flies (Diptera: Simuliidae). 1 records from Novel alpine algae from New Zealand: Chlorophyta. 21 records from BIRDRACE Bon(n)apartemöwen. 16 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del municipio de Pie de Pepe, Chocó. 1346 records from Computarización de material complementario en la Colección Regional de Invertebrados del Pacífico mexicano, Instituto de Ciencias del Mar y Limnología, Unidad Académica Mazatlán, UNAM. 223 records from NatureMap Calcrete Survey. 20 records from Données naturalistes de BONCHE Jérôme. 5 records from A review of Bennelongia De Deckker & McKenzie, 1981 (Crustacea, Ostracoda) species from eastern Australia with the description of three new species. 133 records from Base de datos de fauna batial, abisopelágica y abisal del Golfo de México. 9944 records from natagora-earlybirds. 221 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-MUSCI. 6 records from Biodiversity of spider mites (Acari: Tetranychidae) in Serbia: a review, new records and key to all known species. 2213 records from Hormigas del Museo de Entomología de la Universidad del Valle. 832 records from Elaboration de table de tarif de cubage multispécifique (I). 17 records from Reptiles Specimens of Akita Prefectural Museum. 541 records from Occurrences of Boeckella at high latitudes in the southern hemisphere. 48 records from UWIZM Snakes. 1 records from Chapter 7: Linnaean Plant Names and their Types (part Q). 3 records from A new species of Ledoyerella, L. kunensis sp. nov. (Amphipoda, Senticaudata, Kamakidae) from South West Africa. 4 records from New ants (Hymenoptera: Formicidae) from Micronesia. 15 records from Schulgelände SGD/Viersen. 4 records from A new anchialine species of Naushonia (Decapoda: Gebiidea: Laomediidae) from the Bahamas. 18 records from Swedish Malaise Trap Project (SMTP) - Dermaptera. 850 records from Données du/de la naturaliste ARNABOLDI Frédéric provenant de la base de donnée du SINP Île-de-France CETTIA. 36 records from Flies from L.A., The Sequel: A further twelve new species of Megaselia (Diptera: Phoridae) from the BioSCAN Project in Los Angeles (California, USA). 1209 records from Colecção Entomológica IIA. 73 records from Flora genérica de las gramíneas del estado de Tlaxcala. 6702 records from Antarctic Amphipod Crustaceans: Ant'Phipoda Database (BIANZO). 1 records from 16S sequencing of environmental samples to test the impact of sediment source. 4195 records from MZFC/Coleccion de Aves. 1125 records from Données naturalistes de Ségolène FAUSTEN. 8 records from Collembola Poduromorpha from two littoral areas of northern Rio de Janeiro Brazil. 3 records from New records of phytoseiid mites from Mauritius Island (Acari: Mesostigmata. 17 records from Vibrational Communication Of Isoperla Banks From California And Oregon (Plecoptera: Perlodidae). 1878 records from Natural History Museum Maastricht (NL) - Herbarium. 195 records from Mushrooms Flora of Nepal at Central Department of Botany, Tribhuvan University, Nepal. 1575 records from DMNS Egg Collection (Arctos). 1083 records from MZL Invertebrate Collections. 1298 records from Crustacean specimens of Bihoro Museum. 1681 records from Lepidopterous specimens of Yamagata Prefectural Museum. 319 records from Alterra (NL) - Microarthropods inventory in grassland and arable land. 1173 records from Invertebrates of the river Tana Basin in Kenya available at the National Museums of Kenya's Natural History Collections, Invertebrates Zoology Section. 361 records from Loup 2015 présence occasionnelle communale (réseau Loup-Lynx ONCFS). 21 records from Lebensraum Fluß/Zwickauer Mulde in Wolkenburg. 2990 records from Collection of Coleoptera. 138 records from données arachnologique de LEUCHTMANN Maxime. 5 records from A new species of Pherbellia (Diptera: Sciomyzidae) from Iran. 17 records from Mites of the genus Malaconothrus (Acari: Cryptostigmata) from the British Isles. 5 records from Ostracods (Crustacea) associated with microbialites across the Permian-Triassic boundary in Dajiang (Guizhou Province, South China). 208 records from Chronicle of Nature - Phenology of Mushrooms of Pechoro-Ilych State Nature Reserve. 831 records from Relevés of Main Vegetation Types of the Prioksko-Terrasnyi Biosphere Reserve (2019-2020). 143 records from Orthoptera - SMF. 1655 records from FloVegSI-FAV - Faunistical database of ZRC SAZU. 2408 records from Formación de una base de datos de la biodiversidad de fauna marina y costera en el Golfo de California. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 17 records from Ensemble des données Rhopalocères. 80 records from An updated checklist of aquatic plants of Myanmar and Thailand. 146 records from BioGIS - Bryophytes - HUJ collections. 998 records from Ethnobotanical surveys species in Benin (West Africa). 751 records from Arthropoda Collection of the Seto Marine Biological Laboratory, Kyoto University. 1 records from uncultured prokaryote Targeted loci environmental. 47 records from Inventaire faunistique de l'ENS des Parc des berges de Seine. 861 records from University of Michigan Museum of Paleontology - Vertebrates. 1 records from Contribution to the knowledge of oribatid mites of the genus Austrocarabodes (Acari, Oribatida, Carabodidae) of Madagascar. 252 records from Overvåking av åpen grunnlendt kalkmark i Oslofjordområdet. 608 records from Benthos Chirnov Basin 1986 and 2002. 2018 records from Soil invertebrates occurrences in European North-East of Russia. 88543 records from Queensland Museum provider for OZCAM. 3159 records from Herbarium Universitatis Daugavpiliensis. 85 records from Colección de Entomología - Curculionidae. 3735 records from Données naturalistes de Monsieur LAFAGE Denis. 2 records from The Chinese Folsomia with a description of a new species (Collembola: Isotomidae). 143 records from Universidad del Valle de Guatemala - Colección de Artrópodos (UVGC). 97 records from IPAE egg clutches collection (Aves). 168 records from EDP Baixo Sabor: Herpetology – Baseline Studies [2009]. 3 records from Les Bathypalaemonellidae de Saint-Laurent, 1985 (Crustacea, Decapoda, Caridea) avec description d’une espèce nouvelle et définition d’un genre nouveau. 23 records from Colección Zoológica Universidad del Tolima (CZUT) - Arácnidos. 776 records from Programme ACT : Répartition Pie bavarde 2010 - 2014 Coordonnées GPS Lambert 93. 3391 records from Données d'observations d'orthoptères en Auvergne, d'Emmanuel Boitier, de 1998 à 2015.. 312 records from Vascular Plants from Praia da Vitória (Terceira, Azores, Portugal). 1232 records from Análisis de las relaciones entre las diversidades alfa, beta y gamma a distintos niveles de escala espacial: Procesos históricos y ecológicos que intervienen. V Etapa. 10 records from Ostracods from the ‘ Raibl Beds’ (Carnian, Late Triassic) of Belca section in Karavanke Mountains, northwestern Slovenia. 53 records from Actualización de la base de datos de la Colección nacional mexicana de cultivos microbianos. 10 records from Wildgehege Glauer Tal (Naturpark Nuthe-Nieplitz). 2 records from Type material of land snails (Mollusca: Gastropoda) described from New Zealand by taxonomists in Europe and North America between 1830 and 1934, and the history of research on the New Zealand land snail fauna from 1824 to 1917. 8 records from Electron Micrograph Database - Terrestrial and Limnetic Specimens. 1 records from Insect Collections of Okomu National Park- Nigeria. 49431 records from University of Minnesota Insect Collection. 126351 records from ARABEL - Arachnologia Belgica. 60415 records from Mammal records from Britain from the Atlas of Mammals (1993), with some subsequent records. 70 records from Heinersdorfer Sumpfwiese. 2996 records from Actualización del conocimiento de la diversidad de especies de invertebrados marinos bentónicos de aguas someras (<50m) del Sur del Golfo de México. 29 records from The genus Asiagomphus in Vietnam, with descriptions of three new species, and first descriptions of the male of Asiagomphus auricolor (Fraser, 1926) and of the female of Asiagomphus reinhardti Kosterin & Yokoi, 2016 (Odonata: Gomphidae). 1167 records from Biodiversidad de la Sierra Tarahumara. Lepidoptera: Mimallonoidea, Lasiocampoidea, Bombycoidea y Pyraloidea. 1 records from A new species of the genus Megophrys (Anura: Megophryidae) from Yunnan Province, China. 4909 records from Wolli Creek Preservation Society Bird Survey. 1 records from Rediscovered syntypes of Procrangonyx japonicus, with nomenclatural consideration of some crangonyctoidean subterranean amphipods (Crustacea: Amphipoda: Allocrangonyctidae, Niphargidae, Pseudocrangonyctidae). 348 records from Antarctic pycnogonids. 25 records from Tejidos colectados en el piedemonte llanero, Boyacá - Proyecto Boyacá BIO. 7 records from Inventaire des espèces végétales de la vallée de Gounti Yéna (Niamey). 15148 records from MLZ Bird Collection (Arctos). 9 records from Artsprosjekt Pyrenomycetes. 4 records from Crustáceos del municipio Santa Bárbara, Santander - Proyecto Santander BIO. 616 records from NOAA coral reef monitoring benthic data from sites across Micronesia from 2009-09-29 to 2015-09-25. 30 records from Etude écologique du Parc des Lilas (94). 5 records from Données bibliographiques ASFRA. 21 records from Naturschutzgebiet Müchelholz (Mücheln). 69 records from PRESENCIA DE VISÓN AMERICANO EN TIERRA DEL FUEGO, MAGALLANES, CHILE. 29 records from Wiese am Waldrand (Gurtweil). 41 records from Managing open habitats for species conservation: the role of wild ungulate grazing, small-scale disturbances, and scale - Tanacetum vulgare dominated forb vegetation. 107 records from Fish and crustacean community in the Western Scheldt (Doel nuclear power station) during winter season 1991-1992. 1 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-5. 480 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2018. 17 records from Gastropod Specimens of the Yamagata Prefectural Museum. 3 records from A new species of Odontozona Holthuis, 1946 (Crustacea: Decapoda: Stenopodidea: Stenopodidae) from the Caribbean Sea. 221 records from Butterflies of Singapore and Peninsular Malaysia (Nymphalidae). 9 records from Birdrace-Birding_Bentheim-Grafschaft_Bentheim. 3 records from ImageDOP Bentic Video Annotations in the Faial-Pico Channel in 2011. 22 records from Renaturierung Werse (Innenbereich Beckum). 803 records from Base de datos de las gramíneas (Poaceae) del noreste de México. 241 records from University of Wyoming Museum of Vertebrates (UWYMV) Herpetology specimens. 1 records from Marine bacteria Targeted Locus (Loci). 22 records from Atlas des Hyménoptères Pompilidae du Massif armoricain et des départements voisins : prospections 2018. 10980 records from FUEL - Herbário da Universidade Estadual de Londrina. 1 records from Eine Milbendiagnose aus dem Nachlass Dr. Josef Schweizer. 109 records from Atlantic Forestry Centre Insect Reference Collection. 3696 records from Midden-Limburg Fish Ponds Survey. 8280 records from Dataflos. 9239 records from Dragonfly (Odonata) species records up to 1997 held by Leicestershire Environmental Resources Centre. 2 records from (Supplement Table 3) Percentage cover abundance of plants recorded at the Fell-field Site on Disko Island. 6618 records from Herbarium Senckenbergianum (FR) - Fungi. 1409 records from National System of Protected Areas in Poland - Animals. 8 records from Review of the Eulimnadia (Branchiopoda: Spinicaudata: Limnadiidae) from Argentina with the description of a new species. 167 records from Institut Menorquí d'Estudis. Herbarium Generale Minoricae: HGM. 4 records from A new scale insect host family (Hemiptera: Asterolecaniidae) for Aphytis (Hymenoptera: Aphelinidae) in China. 223 records from Plant specimens of Bihoro Museum. 4 records from Occurrence of mammalia relicts at site Rusenschloß. 110 records from Geometridae de France métropolitaine. 4 records from Is Copytus Skogsberg, 1939 (Crustacea: Ostracoda) a neocytherideid? With description of a new family and two new species. 636 records from Photographs of higher plants, mosses, fungi, lichens, and algae. 30 records from Vegetación asociada a la ciénaga de Bete, municipio del Medio Atrato, Chocó 2008. 151 records from Tejidos de ejemplares colectados en el Páramo de Chingaza - Proyecto Colombia Bio. 9 records from Marine eukaryotes Targeted loci environmental. 3315 records from Leicestershire and Rutland Aculeate Records. 9399 records from CSIRO, Cruises, Vertebrate and Invertebrate Fishery Bycatch, North Australia, 1997. 39164 records from NOAA AFSC North Pacific Groundfish Observer. 23915 records from Formidabel; Belgian Ants Database. 88 records from Observation des insectes sur le territoire de la Métropole Rouen Normandie. 1 records from Effects of Fecal Input, Environmental Conditions, and Environmental Sources on Enterococci Concentrations in an Estuarine Ecosystem. 93 records from Alterra (NL) - Microarthropods inventory in Cranendonck area. 2 records from The genus Lernaeenicus Lesueur (Copepoda, Siphonostomatoida, Pennellidae) in India: a checklist with notes on its taxonomy and ecology. 81 records from Anfibios y reptiles de la Sierra Montenegro-Las Trincheras y el cerro el Chumil, Morelos. 1 records from A checklist of the Cleridae of Iran with new data (Coleoptera: Cleroidea). 2 records from Tejidos colectados en la caracterización biótica para la conservación de especies amenazadas en el área de influencia del Oleoducto Bicentenario, departamentos de Arauca y Casanare, Colombia. 1319 records from RMT Trawl catch from the 1984/85 V5 SIBEX2 voyage. 122 records from ABC event data for Nyika Plateau, Buma Hills. 21633 records from CAS Invertebrate Zoology (IZ). 11 records from Etude d'impact projet d’ouverture de carrière à Vaudoy-en-Brie. 14 records from New taxa of Tateidae (Caenogastropoda, Truncatelloidea) from springs associated with the Great Artesian Basin and Einasleigh Uplands, Queensland, with the description of two related taxa from eastern coastal drainages. 3 records from Review of Campsicnemus species from the Atlantic Ocean Islands (Diptera: Dolichopodidae). 26 records from Macroinvertebrados bentónicos de playas de arena (Monte Hermoso-Pehuen Có, Buenos Aires, Argentina). 417 records from NW Pacific Deep-sea Benthos Biodiversity (Beneficial Project). 66 records from Colección Aracnológica del IADIZA-CCT CONICET Mendoza: IADIZA-CAI. 6 records from There are 3 zooplankton samples from 3 different ponds, we collected sample and use the fresh samples to do DNA extraction directly, then mix them with adjustment guided by the number of species within each of them. At last, use Hiseq-2599 PE-150 to do NGS work. 15646 records from Insects, Outer Hebrides. 829 records from Taxonomía y distribución de los filópodos (Crustacea: Branchiopoda, Anostraca, Notostraca, Spinicaudata y Laevicaudata) de México. 90 records from Suivi des leucorrines sur le site du Marais du Plata. 6987 records from ALCB herbarium - Universidade Federal da Bahia - Herbário Virtual REFLORA. 12 records from An der Ohm, (Wettsaasen). 5170 records from EDP Baixo Sabor: Construction and Reservoir Filling Phases – Vascular Flora and Habitats: species of conservation concern (RELAPE) - [2010-2014]. 1 records from Community structure of Archaea in the western North Pacific and the Arctic Ocean. 11 records from Philippine Mollusk Symbiont - ICBG Collection. 125 records from Inventaire des odonates d'intérêt communautaire. 177 records from Bryophytes specimens of Okinawa Prefectural Museum & Art Museum. 81 records from Restauración de flora y repoblamiento de fauna nativa en 1,000 hectáreas para el restablecimiento del corredor biológico costero en la Laguna Madre, Tamaulipas. 208 records from Données de la collection de Hubert Piguet - Famille des Elateridae. 991 records from BioGIS - Vascular plants - Israeli Gene Bank. 344 records from Flora de las sabanas inundables de las cuencas de los ríos Bita, Manacacías y Cravo Sur - SULU II. 225 records from Kenai National Wildlife Refuge, Alaska (KNWR) Bird observations (Arctos). 983 records from Distribution Atlas of Butterflies in Ireland 1979 (An Foras Forbartha). 746 records from NSW South Coast & ACT plants. 2 records from Les Ostracodes de la falunière de Grignon (Lutétien du Bassin de Paris): implications stratigraphiques. 1344 records from EDP Baixo Sabor: Birds - Construction and Reservoir Filling Phases - Vilariça Stream (MC1) [2013-2014]. 3 records from Abundance of birds in the Lena Delta Region. 6 records from Kirkliston Range stream monitoring. 50 records from 16S rDNA amplicon of Bacteria and Archaea Metagenome. 5 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Squamata (no Serpentes) (MFA-ZV-Sq). 1 records from Acantorna-a new genus of Hymedesmiidae (Porifera, Demospongiae Poecilosclerida) from the western Aleutian Islands of Alaska with description of Acantorna tahoma n. sp.. 11184 records from NEOTROPICMYXO. A database of Myxomycetes from the Neotropics. 4 records from Ortsrand Zandershagen. 7 records from An der Weida zwischen Talsperre Zeulenroda und Vorsperre Weida. 821 records from Crickets of the genus Gryllus in the United States (Orthoptera: Gryllidae: Gryllinae). 2761 records from Akita Prefectural Museum, Observation Records of Birds in Akita Prefecture. 4613 records from South Dakota State University, The Severin-McDaniel Insect Research Collection. 337 records from Colección Ornitológica de la Universidad del Valle. 174 records from Chronicle of Nature - Phenology of Insects of State Nature Reserve Kivach. 36 records from Minute but constant morphological differences within members of Stenothoidae: the Stenothoe gallensis group with four new members, keys to Stenothoe worldwide, a new species of Parametopa and Sudanea n. gen. (Crustacea: Amphipoda). 66 records from Chronicle of Nature - Phenology of Plants of State Nature Reserve Privolzhskaya Lesostep. 2 records from A new species of Limnonectes (Amphibia: Anura: Dicroglossidae) from Vietnam. 121 records from Registros de dípteros asociados al proyecto: Estratificación espacial del dengue basado en la identificación de factores de riesgo en el departamento del Cauca. 4 records from Parasitic copepods infesting the olfactory sacs of skates from the southwestern Atlantic with the description of a new species of Kroeyerina Wilson, 1932. 10 records from Inventaire naturaliste de la commune de Papaichton (Guyane) : mission 2018. 1116 records from Fungal literature records database of the Southern West Siberia (Russia). 202 records from Living Cirripedia. 183 records from Helmintos parásitos de peces del sureste de México. 1 records from Zur Oribatidenfauna des Leopoldsberges von Wien (1. Beitrag). 20 records from Naturpark Kottenforst-Ville 15.6.09. 1 records from Madangella altirostris, a new genus and species of palaemonid shrimps (Crustacea: Decapoda: Palaemonidae) from Papua New Guinea. 170 records from ConDidact Citizen Science Surveys - Spiders 2011. 56 records from Amundsen Gulf Overwintering Eukaryote Community. 116 records from Tree species composition of natural forest islands in a savanna matrix in the northern Brazilian Amazonia. 18 records from Lepidepecreoides stoddartae sp. nov. from the Falkland Islands (Amphipoda: Tryphosidae). 16 records from Roter Berg Werdau (Leubnitz). 64 records from The Belgica 121 expedition to the Western Antarctic Peninsula: a high resolution biodiversity census. 4 records from A new species of the hermit crab genus Alainopaguroides McLaughlin, 1997 (Crustacea: Decapoda: Anomura: Paguridae) from the South China Sea. 2879 records from Données naturalistes de Charlotte PICARD. 4 records from Ostracoda abundance of Hole 44-390. 131 records from Manejo campesino sustentable del maguey papalote del Chilapan. Fase II. 4288 records from University of Nebraska State Museum Birds Collection. 44 records from FFH-Gebiet Klosterwasser/Burkau. 2 records from BCCM/ULC Cyanobacteria culture collection at the University of Liège (ISO9001 certified). 6390 records from University of California Santa Barbara Invertebrate Zoology Collection. 53 records from Données naturalistes de Hubert GUIMIER. 298 records from Données naturalistes de Hervé BOUYON. 86 records from Données de la collection Rousset -1947-2013. 1 records from The Shiny Cowbird, Molothrus bonariensis (Gmelin, 1789) (Aves: Icteridae), at 2,800 m asl in Quito, Ecuador. 26 records from Données du/de la naturaliste D'HINZELIN MARCEL provenant de la base de donnée du SINP Île-de-France CETTIA. 5 records from Ten new species of the spider genus Pholcus Walckenaer, 1805 (Araneae, Pholcidae) from Southeast Asia. 1 records from Neue Milbenarten aus Kärnten. 4 records from Thistle Heads and Ermerged Insects. 56 records from CSIRO Yellow Box Fragmentation Project. 5 records from Psychotria niauensis sp. nov. (Rubiaceae), espèce calcicole endémique de la Polynésie française, décrite de l’atoll soulevé de Niau (Tuamotu). 453 records from The hoverfly collection (Diptera, Syrphidae) of the International Institute of Tropical Agriculture (IITA) at Calavi (Benin). 796 records from Weddell Sea macrozoobenthos EASIZ I. 17 records from A new South American species of Banasa Stål (Hemiptera: Heteroptera: Pentatomidae: Pentatominae): from egg to adult. 39 records from sea water Picoeukaryotic Community Raw sequence reads Raw sequence reads. 175 records from Modelos predictivos de distribución geográfica para Spizella wortheni, Cynomys mexicanus, Vulpes macrotis zinseri y Taxidea taxus berlandieri. 4 records from Ostracod species in Oligocene sediments of core CRP-3. 9 records from Records of pine martens from SNH casework reports and licence applications, 2005 - 2016. 1611 records from Fauna y flora en áreas con cultivos de palma de aceite en el norte y oriente de Colombia. 71 records from Bringing Reedbeds to Life Water Vole and Mink Survey of five key reedbed sites in England in 2009, 2010. 458 records from Données du/de la naturaliste Chevreau David provenant de la base de donnée du SINP Île-de-France CETTIA. 432 records from Communauté_de_communes_Asse_Bléone_Verdon_2017_12_18. 2 records from Occurrence of mammalia relicts at site Climauti II. 8 records from Seawater metagenome Targeted loci environmental. 7 records from Phytoplankton abundance measured on water bottle samples at station PS65/545-1. 10 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/092-3. 3 records from Art´n Vielfalt im Kinderwald. 27 records from Waldi-Weiher. 5 records from Herpetofauna de la expedición Pisba - Proyecto Boyacá BIO UPTC. 52 records from UF Environmental Archaeology Tick Island Zooarchaeological Data. 219 records from Invasive Non-Native Species, Outer Hebrides. 6275 records from Phase 2 Lowland Grassland Survey of Wales. 77 records from Gewann Krampf (Heilbronn). 67993 records from hymenoptera. 111655 records from Naturalis Biodiversity Center (NL) - Crustacea. 129 records from Amphibian and Reptilian (KIEE-AR). 16 records from Naturschutzgebiet Lippeaue (Marl) - Pfadis in Sickingmühle. 10705 records from Danish Ants (Formicidae). 2 records from Studies on Neotropical crickets: New species and notes on the classification of Field Crickets genera Anurogryllus and Gryllus (Orthoptera: Gryllidae: Gryllinae). 1 records from A new species of Pestalotiopsis from leaf spots of Licuala grandis from Hainan, China. 50 records from Inventory of Bassila forest (North-Benin). 370 records from Fauna and population of oribatid mites (Acari, Oribatida) in the vicinity of Kosogorsky metal works (Tula Region, Russia). 68 records from Pollen profile from Muscotah Marsh B. 251 records from (Table 2) Abundance of ostracods in surface sediment samples from the Admiralty Bay, King George Island, West Antarctica. 4 records from Visual Plants (144.41.33.158) - Private collection of Asta Napp-Zinn. 3 records from The larva of Lestes alfonsoi Gonzalez & Novelo (Zygoptera: Lestidae). 70 records from The genus Hoplothrips in Australia (Thysanoptera, Phlaeothripinae), with eleven new species. 315 records from Palaeobiology collection, FAU Erlangen. 14254 records from Georgia Southern University - Savannah Science Museum Herpetology Collection. 171162 records from CLICNAT Base de données naturaliste picarde gérée par Picardie Nature. 32133 records from Leicestershire and Rutland Environmental Records Centre records 2015-2019. 48516 records from DATAVES. 9 records from seawater metagenome Metagenome. 12 records from Herpetofauna asociada a la cuenca del río Quito - Chocó, 2014. 2 records from A new species in the genus Alopecosa Simon, 1885 from Korea (Araneae: Lycosidae). 885 records from (Appendix 8) Distribution of barnacles, bivalves, gastropods, and calcified worm tubes in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 1 records from ATCC Bacteria Collection Catalog. 43 records from Heliconiine Butterfly Collection Records from University of Cambridge. 541 records from The Broward College Insect Collection. 89 records from Composición y estructura de la ornitofauna de la reserva de la biósfera Pantanos de Centla. 64 records from SNH Invertebrate Site Condition Monitoring 2013/14: Earlshall Muir SSSI. 1 records from A new Camponotus from Madagascar and a small collection of ants from Mauritius.. 19 records from Colección de Líquenes Austroamericanos Ex Herbario Regnelliano- FML. 3401 records from Berea College, Ralph L. Thompson Herbarium. 6 records from Macrohongos de los bosques montanos del Oriente Antioqueño, Cañón del río Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 38 records from (Table 2) Species density and composition of an inshore and offshore station in Kongsfjord, Svalbard. 33 records from Tejidos colectados en el páramo de Pisba, Boyacá - Proyecto Boyacá BIO. 9 records from Birdrace-Bielefinken-Bielefeld. 2252 records from Ecosphère_2017_12_18. 1615 records from Kenai National Wildlife Refuge, Alaska (KNWR) Insect specimens (Arctos). 121 records from Range table from ostracoda in ODP Hole 143-866B. 20 records from Müritz-Nationalpark. 62 records from Flora vascular y no vascular:expedición El Consuelo - Proyecto Boyacá BIO UPTC. 11 records from A new species of Leioseius (Acari: Ascidae) from Brazil, redescription of Leioseius basis and a key for separation of the world species of the genus. 1 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-2. 74 records from (Table 8) Distribution of ostracode species in surface sediments of the eastern Laptev Sea. 1 records from First record of Cephenniitae in the Bismarck Archipelago, Papua New Guinea, with description of new species of Cephennodes and Cephennomicrus of Mussau and Manus Islands (Coleoptera, Staphylinidae, Scydmaeninae). 479 records from Colección Limnológica Universidad de Antioquia. 378 records from Rock ptarmigan (Lagopus muta) radio telemetry in Lierne, Norway. 14 records from Birdrace-Wannacks_Topti(c)ker-Lübeck. 10947 records from Fermanagh Flora. 46 records from Wald am Schloss Wittgenstein Bad Laasphe. 11610 records from Actualización y enriquecimiento de las bases de datos del proyecto de evaluación y análisis geográfico de la diversidad faunística de Chiapas. 9860 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 3 records from Metrocoris sikkimensis sp. nov. (Hemiptera: Heteroptera: Gerridae) from northeastern India, with a key to species of the compar group occurring in India. 518 records from Conservación y monitoreo de anfibios en riesgo de extinción en Chiapas. 146 records from Données naturalistes de LUPOLI Roland. 19 records from Données du/de la naturaliste JOSSERAND oriane provenant de la base de donnée du SINP Île-de-France CETTIA. 59 records from Floristic records in the Moscow and Novgorod regions. 354 records from Weber State University Herbarium. 128 records from Inventarios de la biodiversidad en el piedemonte subandino de Yopal. 14 records from Données de la naturaliste Anna Even. 21 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2008. 76 records from Données naturalistes de François BRETON. 77 records from Espèces végetales sur sable roux du fourré de Ranobe, PK 32 Toliara. 4 records from Rare And New For The Fauna Of The Russian Far East Spiders (Aranei). 2 records from A new slipper lobster of the genus Petrarctus Holthuis, 2002 (Crustacea, Decapoda, Scyllaridae) from Southwest coast of India. 480 records from Coral Reef Evaluation and Monitoring Project Florida Keys 1998. 1 records from A new stenochirid lobster (Crustacea, Decapoda, Stenochiridae) from the Early Jurassic of France. 4270 records from Museu Paraense Emílio Goeldi - Ophidia Collection. 68 records from (Table 2) Ostracoda abundances in sediment core PS2185-6 (Lomonosov Ridge). 7 records from Biodiversity of anuran endoparasites from a transitional area between the Atlantic Forest and Cerrado biomes in Brazil: new records and remarks. 10 records from Copepoda (Siphonostomatoida: Dirivultidae) from Hydrothermal Vent Fields on the Central Indian Ridge, Indian Ocean. 2 records from Kystfuruskoger i Tysnes og Fusa. 60 records from Centre d'Estudis Avançats de Blanes, Macroinvertebrados Limno. 4188 records from EDP Foz Tua: Terrestrial Birds, Winter (point counts) - Ecological Monitoring Program [2011-2017]. 3 records from Die Bachspezies 2008/2009. 1 records from Tucurui_Metagenoma_MGRAST. 4154 records from Lepidoptera specimen database of Japan. 1761 records from Leicestershire and Rutland Reptile Records to 2011. 4 records from Haematophagous biting midges of the extant genus Culicoides Latreille (Diptera: Ceratopogonidae) evolved during the mid-Cretaceous. 212 records from Censos de aves en los municipios de Honda (Tolima) y Guaduas (Cundinamarca) - Reexpedicion Chapman. 12509 records from Système d’Information Régional sur la Faune et la Flore - FNE Centre-Val de Loire - Données 2016. 2 records from Abundance of benthos infauna at station GIK23042-2. 10 records from Streuobstwiese. 42 records from An Online Database of the Immatures of Coleoptera (Arthopoda, Insecta) Described from Brazil. 267 records from Weeds Australia. 1 records from Die vom k. k. Oberartze Herrn Dr. Justyn Karlinski im Jahre 1887 in Bosnien, der Herzegowina und in Novibazar gesammelten Myriopoden. 852 records from Waarneming.nl (NL) - Great Grey Shrike Count 2009-2010. 46 records from MBON POLE TO POLE: ROCKY SHORE BIODIVERSITY OF GORGONA ISLAND. 1275 records from Alterra (NL) - Microarthropods inventory in calcareous grasslands. 3 records from A new species of Caenis Stephens, 1835 (Ephemeroptera: Caenidae) from Tamil Nadu, Southern India. 58 records from Chronicle of Nature - Phenology of Birds of Central Forest State Nature Biosphere Reserve. 200 records from British Reptiles & Amphibians in the collections of World Museum Liverpool. 453 records from Vermont Orthoptera Records from Historic Dot Maps. 3905 records from Inventario y catálogo de ostrácodos recientes de los mares mexicanos. 139883 records from NatureServe Network Species Occurrence Data. 2042 records from Colección de Geraniales hasta Lamiales del Museo Botánico CORD - IMBIV. 34 records from Données naturalistes de Renaud PUISSAUVE. 21 records from Suivi ornithologique par IPA et IKA réalisés dans la Réserve nationale de l’Étang de Saint-Paul en 2012 et 2014. 173 records from Pollen analysis of sediment profile HAE10 from Hämelsee. 137 records from New species of Culex (Culiciomyia) (Diptera: Culicidae) from Talangaye Forest in Cameroon and descriptions and identification keys for males of the Afrotropical species of the subgenus. 26 records from Contribution to the Asian and Afrotropical species of the genus Dyschiriodes (Coleoptera: Carabidae: Scaritinae). 597 records from The Gibson spider collection. 2750 records from Instituto Pirenaico de Ecología-CSIC: Herbarium JACA. 74 records from AMNH Invertebrate Paleontology WIS-Cretaceous Research Collection. 23 records from Naturgrundstück (Eutin). 117 records from Three new species of Oxypoda from Spain, Armenia, and Ukraine with notes on the fauna of Armenia (Coleoptera: Staphylinidae: Aleocharinae). 68 records from Description of a new Penaeidae (Decapoda: Dendrobranchiata) species, Farfantepenaeus isabelae sp. nov.. 45 records from Truppenübungsplatz Panzerkaserne Böblingen. 3 records from A New Species of Cryptopontius (Crustacea: Copepoda: Siphonostomatoida) from Easter Island. 53 records from The Calliphoridae (Diptera) of Armenia. 109 records from Réseaux écologiques/Trame verte et bleue. 25 records from Korean Plant Virus Database. 37 records from données araneologiques de LEENKNEGT Virginie. 1 records from Coelenterata (Cnidaria and Ctenophora) collection of National Museum of Nature and Science. 3 records from Zoology in the Middle East. 523 records from Pollichia Pilzherbar. 402 records from Herbario virtual bosques secos de Colombia - Sección herbario ICESI. 837 records from Segunda caracterización biológica de aves del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 27858 records from Données de l'Observatoire de la Faune de Bourgogne. 1008 records from Colección Herpetológica (Reptiles) del Museo de Historia Natural de la Universidad Industrial de Santander. 577 records from Fungi of parks, forests and reserves of New Jersey, 2018. 147773 records from Wild bees of Belgium. 21 records from Données du/de la naturaliste Villalta Rémi provenant de la base de donnée du SINP Île-de-France CETTIA. 38 records from Phenological Center - Birds (Murmansk). 1 records from Developmental Biology among Corbiculate Bees: Bombus impatiens, Including Observations on Its Egg Eclosion. 10 records from Mammals of the Natural Laboratory of Peat-Swamp Forest, Sebangau, Central Kalimantan, Indonesia. 13 records from Mokihinui and Karamaea small tributaries and seeps. 1349 records from Anillamiento de Aves Sierra Nevada de Santa Marta - Proyecto Cruzando el Caribe. 1224 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 2 records from Aspilanta new genus (Heliozelidae) specimen data. 1 records from Patterns of head shape and scutellation in Drymarchon couperi (Squamata: Colubridae) reveal a single species. 114 records from If_Ecologie_Conseil_2017_12_18. 4 records from Reassessment of the taxonomic status of Pseudopaludicola parnaiba (Anura, Leptodactylidae, Leiuperinae), with the description of a new cryptic species from the Brazilian Cerrado. 202 records from Rescate de epífitas Oleoducto Bicentenario, Tramo Araguaney - Banadía (rescate). 19 records from Molecular and morphological identification of pistachio armored scale insects (Hemiptera: Diaspididae), with description of a new species. 26668 records from Allan Herbarium (CHR). 368 records from Biological Recording in Scotland - Bumblebee Survey. 3 records from Analyses of the recent components of sediment core PS1011-1. 7935 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 297 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Plantas Tapachula). 1591 records from Royal British Columbia Museum Entomology Collection. 4329 records from Actualización de la base de datos de hongos macroscópicos de Jalisco. 27 records from Two new species of freshwater crayfish of the genus Faxonius (Decapoda: Cambaridae) from the Ozark Highlands of Arkansas and Missouri. 61 records from Monitoreo biológico en la cuenca La Paila, campaña ARA - RARE - CVC – Asociación Calidris. 42 records from Quarrendorfer Landschaftsschutzgebiet. 13 records from Insectos en el municipio de San Juanito, Meta - Colombia BIO. 797 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Herpetológica Chetumal). 20 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 4340 records from EDP Foz-Tua: Large Mammals (diurnal transects): Ecological Monitoring Program [2011-2017]. 24470 records from Estonian University of Life Sciences Institute of Agricultural and Environmental Sciences Mycological Herbarium. 7 records from Out on a limb: novel morphology and position on appendages of two new genera and three new species of ectoparasitic isopods (Epicaridea: Dajidae) infesting isopod and decapod hosts. 40 records from Chironomid remains in the sediment sequence of Site PG1212. 1 records from MGC Herbarium of University of Malaga (Spain): MGC-Algae dataset. 1 records from First records of Nacerdes melanura (Linnaeus 1758) and Xanthochroina auberti (Abeille de Perrin 1876) (Coleoptera: Oedemeridae) from Israel. 1 records from Dryinidae and Embolemidae (Hymenoptera, Chrysidoidea) from Anijima, Ogasawara Islands, Japan. 28 records from BMHS Crustacean Collection. 483 records from Lista florística de la Costa Grande del estado de Guerrero. 4 records from Disentangling the Pelomedusa complex using type specimens and historical DNA (Testudines: Pelomedusidae). 1 records from Espèces envahissantes de la Guinée forestière extraites dans la base de données de CRRA Sérédou Macenta, IRAG.. 20 records from Helmintos parásitos de peces dulceacuícolas de cuencas hidrológicas del Centro-Norte de México (Durango). 2 records from Composición florística de áreas degradadas por actividad minera a cielo abierto en el municipio de Condoto-Chocó, como insumo para calcular la biomasa vegetal, 2017. 2 records from Equatorial Pacific Ocean Targeted loci environmental. 21833 records from MDFRC macroinvertebrate survey. 57 records from Données naturalistes de Pauline BALDUCCI. 194 records from Review of the Spirobolida on Madagascar, with descriptions of twelve new genera, including three genera of ' fire millipedes' (Diplopoda). 548191 records from Swiss National Databank of Vascular Plants. 10 records from Amtsrain Apolda-Zottelstedt. 9 records from Inventaire des reptiles 2014. 11 records from PROJET DE CONSTRUCTION D’UNE ROUTE DE TRANSPORT DES MINERAIS DE BAUXITE DE GAC: EIES, inventaire des amphibiens (CESP2016-022). 6844 records from DIBA-Parc del Montnegre i el Corredor. 4 records from Données du/de la naturaliste LELARDOUX LOIC provenant de la base de donnée du SINP Île-de-France CETTIA. 57359 records from University of Tartu Natural History Museum and Botanical Garden Zooloogical Collections. 173 records from MoJ BioBlitz August 2018. 2 records from Two new pill millipedes (Diplopoda: Glomerida: Glomeridae) from high mountains of Vietnam. 589 records from Programme ACT : Répartition Pie bavarde 2005 - 2009 Coordonnées GPS Lambert 93. 539 records from Diversidad y dinámica del fitoplancton marino en la bahía de Acapulco, Guerrero. 328 records from JRS Wetands data Rwanda, 2019. 46 records from A New Species Of Isoperla Banks (Plecoptera: Perlodidae) From The Southern Appalachians, With Notes On The I. Montana Group. 1085 records from Muséum_de_Toulon_et_du_Var_2017_12_18. 29 records from On species of the genus Macrosaldula (Hemiptera: Heteroptera: Saldidae) of the Palaearctic Region, with description of M. graziae sp. nov.. 1548 records from EDP Baixo Sabor: Bat Roosts - Ecological Monitoring Program (PME) (2008-2014). 9 records from Redefinition of Nipponbathynella based on the four new species from East Asia (Crustacea: Bathynellacea: Parabathynellidae). 2 records from Cepario de Microorganismos y Hongos Filamentosos de la Universidad del Valle. 6 records from Grundwasserlebensraum im Englischen Garten (München). 1001 records from Herbario de la Sociedad Micológica Barakaldo Mikologia Elkartea. 208 records from Crustacea in surface sediments off Sylt collected during HEINCKE cruise HE218. 19 records from Catalogue of the Syrphidae of Egypt (Diptera). 4 records from Fish Collection of National Museum, Philippines. 10 records from A new species of the swimming crab genus, Laleonectes Manning & Chace, 1990 (Crustacea: Brachyura: Portunidae), from the western Indian Ocean. 450 records from Invertebrados del Parque Nacional Arrecife Puerto Morelos. 32 records from Occurrence of mammalia relicts at site Stadel im Hohlenstein. 102 records from Review of East Palaearctic species of Sympycnus Loew, 1857, with a key to species. 231 records from The Collection of Lichenicolous Fungi at the Botanische Staatssammlung München. 778 records from Colección de insectos de importancia médica del Instituto Nacional de Salud - Ceratopogonidae. 2997 records from Inventaire de la flore de Charente-Maritime 2017. 294 records from Colección Thomas G. Zoebisch asociada a la Colección Entomológica del Centro de Estudios en Zoología (Mexicanos). 5 records from Caracterización Ecológica de los Macroinvertebrados de las Fuentes Hídricas presentes en el Cerro Jánano. 14584 records from MCP - Coleção de Abelhas. 248 records from Données du naturaliste Bussac Augustin provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from Erhard Sopp. 95 records from Die Oribatiden-Arten (Acari) eines suedwestdeutschen Buchenwaldes I.. 2 records from Taxonomic studies on potter wasps (Hymenoptera: Vespidae: Eumeninae) of south India. 3 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE206. 11923 records from Entomology Collection at the Natural History Museum of Utah. 4 records from Four new Megaselia species (Diptera: Phoridae) from animal carcasses in Bangi, Malaysia. 987 records from Colección de Fabales del Museo Botánico CORD - IMBIV. 40 records from makran-chabahar-arthropods. 694 records from Données DREAL Centre-Val de Loire - Faune - 2018. 245 records from Colección Herpetológica de la Patagonia. 42 records from Hartland Nature Club Lepidoptera Collection. 8244 records from Locations of plants on dot distribution maps in the Flora of Siberia (Flora Sibiraea, 1987–1997). 4 records from On Plesionika persica (Kemp, 1925) and P. reflexa Chace, 1985 (Crustacea: Decapoda: Pandalidae) from India. 16149 records from ALCB - Herbário Alexandre Leal Costa. 11 records from BIRDRACE LiLaLau. 250 records from Herbarium specimens of Limoges university (LIMO). 53495 records from Tetraonid line transect surveys from Norway: Data from Fjellstyrene. 23 records from UTEP Invertebrates (Arctos). 1713 records from Diptera Collection of Museum and Institute of Zoology PAS. 114 records from Pseudoscorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 18 records from Schulteich Freie Waldorfschule Darmstadt. 449 records from Highland bird data 2002 - 2003 - non-breeding records. 594 records from Harriet Irving Botanical Gardens (HIBG). 25 records from Inventario de Flora de la Reserva Forestal Protectora Regional Cuchillas del Tigre, El Calón y La Osa. Municipios de San Francisco y Sonsón-Antioquia.. 7775 records from 1994-2020 Capercaillie Cold Searches Data, Scotland. 20 records from ABC_Ndangopuma_hills_eventdata_25_11_2005. 151 records from Korean Ethnobotany Database. 1349 records from Weed and native flora data for the Swan Coastal Plain. 167 records from Herbario MAIA, colección Flora Forestal del INIA-CIFOR. 20 records from New records of the larval forms Cerataspis monstrosa and Amphionides reynaudii (Crustacea: Decapoda) from the western tropical Atlantic. 3 records from Fototrampeo al interior de las áreas del Banco de Hábitat del Meta de Terrasos. 34 records from MGYS00005313. 3843 records from CNIN/Abejas de México/Apoidea. 570 records from RNF - Données du Parc Naturel Régional du Vercors. 17 records from Crustacea specimens of Kuroshio Biological Research Foundation. 198 records from Flora útil del Municipio de la Huerta, Jalisco. 1170 records from Insectes Hyménoptères Scollidés de France. 677 records from Ensemble des données Odonates. 2664 records from Family Geraniaceae in CSBG SB RAS herbarium collections (NS, NSK). 153 records from Diversité et distribution de quelques espèces de plantes agroforestières au Bénin. 9 records from First record of the genus Agnara (Isopoda: Oniscidea) from Iran with descriptions of two new species. 69 records from SPC CoFish Invertebrates Observations Marshall Islands 2007. 93 records from South Lanarkshire peatland records 2013. 14 records from The Amphibians of the Mitaraka massif, French Guiana. 12601 records from Suivi Temporel des Libellules (STELI). 32 records from Données du/de la naturaliste GAUTHIER Nicolas provenant de la base de donnée du SINP Île-de-France CETTIA. 252 records from Herpetological (amphibian & reptile) specimens of Ryukyu University Museum (Fujukan). 252 records from Derbyshire Casual LEPIDOPTERA records - Casual records collated by Derby Museum.. 136 records from Transferts SI Faune - Données naturalistes opportunistes de Cedric DEVILLEGER. 664 records from Museo Nacional de Ciencias Naturales, Colección de Aves: MNCN-Ornit. 211949 records from First Bird Atlas. 711 records from Universidad Autónoma de Madrid, Madrid; Lepidópteros. 9313 records from Herbarium Specimens of Tokushima Prefectural Museum, Japan. 10 records from Oxygen minimal zone Targeted loci environmental. 22 records from Revision of Family Megacalanidae (Copepoda: Calanoida). 65 records from Reptilia ZMK. 1 records from Xibalbanus cozumelensis, a new species of Remipedia (Crustacea) from Cozumel, Mexico, and a molecular phylogeny of Xibalbanus on the Yucatán Peninsula. 132 records from Plant observations from Białowieża National Park. 40 records from New distributional records of Staphylinina in Taiwan, including a new species of Miobdelus Sharp (Coleoptera: Staphylinidae: Staphylininae: Staphylinini). 200 records from Diversity of Spiders from Azorean Trails. 12 records from Ensemble des données Orthoptères. 441 records from The bees of Lebanon (Hymenoptera: Apoidea: Anthophila). 2546 records from Dynamics of Collembola communities in a spruce-linden forest with mosses and sedges by layers (1973-1977). 1320 records from Inventaire de la flore de Charente-Maritime 2018. 499 records from Census of plant species in Pahou forest reserve. 10 records from Agrarian stands of Irvingia gabonensis Aubry-Lecomte ex O'Rorke) Baill. in the department of Couffo in South Benin (West Africa). 44 records from Computarización de la colección de myxomycetes y líquenes de Baja California. 334 records from Pollen profile RAC20, Lake Racou, France. 28 records from Chronicle of Nature - Phenology of Insects of Tigirek State Nature Reserve. 69 records from Lillachtal mit Kalktuffquelle bei Weißenohe. 93 records from Natura 2000 Vallée de la Seille. 1 records from The taxonomic implication of frontal tubercles in Polypedilum subgenera diagnoses, with re-description of Polypedilum isigabeceum Sasa & Suzuki (Diptera, Chironomidae). 1223 records from Inventario de Hymenóptera; parasítica en México. 32 records from VSN-Wiese. 7 records from New records of Chalcidoidea (Hymenoptera) from the Maltese Islands with an updated checklist. 23 records from Additions to the list of Finnish Bibionomorpha (Diptera, Nematocera). 13918 records from Alien plant presence dataset from the point-radius plot surveys in 2010-2015 in Taiwan. 138 records from MfN - Fossil Fish Collection. 148 records from Colección de insectos agrícolas del proyecto diversidad en sistemas de cultivos. 2 records from A new species of Liriomyza Mik (Diptera, Agromyzidae) on okra in Brazil. 1602 records from Ibaraki Nature Museum, Fungi collection. 2883 records from Colección de Reptiles - Museo de Herpetología de la Universidad de Antioquia. 31 records from Relative abundance of ostracods in sediment core Sv09. 613 records from Chironomid Specimen records in the Chironomid DNA Barcode Database.. 35 records from Ecological study of the plankton in the port of Ostend in 1965. 231 records from Museu Valencià d′Història Natural - Fundación Entomológica Torres Sala: FETS. 13090 records from Amis_des_Marais_du_Vigueirat_2017_12_18. 32 records from A new species of long-legged terrestrial Terrapotamon Ng, 1986 (Crustacea: Brachyura: Potamidae) from limestone formations in Satun, southern Thailand. 46 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Bryozoa. 11 records from BIRDRACE Nachtigallen. 16 records from A New Species Of Perlesta (Plecoptera: Perlidae) From North Carolina With Additional Records For North Carolina And Virginia. 618 records from ConDidact Citizen Science Surveys - Amphibians 2007. 2 records from Données de Midi-Pyrénées transmises par Pascal Peyrache.. 6 records from Données naturalistes de THÉVENOT Jessica. 9 records from Occurrence of mammalia relicts at site Biedermann. 56 records from Biodiversidad del orden Araneae (Arachnida) de las Islas del Golfo de California, México. 1888 records from Trondheim urban biodyversity survey. 4276 records from Inventaire de la flore de Lot-et-Garonne 2017. 57 records from Données du/de la naturaliste LUSTRAT Philippe provenant de la base de donnée du SINP Île-de-France CETTIA. 115 records from SNH Invertebrate Site Condition Monitoring 2013/14: Glenmore Forest SSSI. 7 records from Phytoplankton abundance measured on water bottle samples at station PS65/514-2. 512 records from Colección Botánica-Herbario. Museo de Ciencias Naturales y Antropológicas “Juan Cornelio Moyano” (Mendoza, Argentina). 28 records from New species of Hercostomus Loew, 1857 from Afrotropics (Diptera: Dolichopodidae) and key to Afrotropical fauna. 1140 records from Estación Biológica de Doñana - CSIC, Anfibios. 2451 records from R. L. McGregor Herbarium Lichen Collection. 9 records from Peces pelágicos de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 50 records from Clyde Breeding Bird Tetrad Atlas 1985 - 1991 - sensitive species. 28106 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 5 records from Cave-dwelling crabs of the genus Karstarma from lava tubes of the volcano ‘ Piton de la Fournaise’, in Réunion Island, with description of a new species and redescription of Karstarma jacksoni (Balss, 1934) from Christmas Island (Decapoda, Brachyura, Sesarmidae). 5048 records from Oregon Bee Atlas Survey Data: 2018. 56 records from Birds Specimens of Akita Prefectural Museum. 2 records from UAM Fish Collection (Arctos). 2 records from Delimiting the snapping shrimp Alpheus lobidens De Haan, 1849 (Caridea: Alpheidae) based on morphological and molecular data. 3 records from University of Sargodha Herbarium. 8808 records from Survey of bumblebees in central Alberta - 2018. 7 records from Données naturalistes de LE GLOANEC Vincent. 6062 records from Calf of Man (Isle of Man) Bird Observatory Daily Logs, 1959-67, 1969-81. 218 records from Protist Diversity in the East China Sea. 22 records from Données espèces - Expertise IPE 79. 8 records from Mesostigmatic mites (Acari: Mesostigmata) of Saudi Arabia (excluding Phytoseioidea), new records and a key to the known species. 328954 records from NBIS Records to December 2016. 29 records from SPC PROCFish/C Invertebrates Observations Kiribati 2004. 78 records from Rohrmeistereiplateau und angrenzendes Gebiet. 350 records from Floral visits on plants, InsectScale 2008. 16 records from (Table 1.2.1.1) Abundance of sympagic meiofauna of sea-ice core PS69/574-1. 904 records from Survey and monitoring records for Scottish Wildlife Trust reserves from reserve convenors and Trust volunteers - Unassessed data. 18 records from An interactive key to Central European species of the Pteromalus albipennis species group and other species of the genus (Hymenoptera: Chalcidoidea: Pteromalidae), with the description of a new species. 64 records from South American Antarctic Marine Biodiversity Literature. 33531 records from Arizona State University Vascular Plant Herbarium. 1157 records from A grid database on vascular plant distribution in the Meshchersky National Park, Ryazan Oblast, Russia. 18 records from Métropole_Nice_Côte_d'Azur_2017_12_18. 2 records from City of Edinburgh Natural Heritage Service - Large Red Damselfly Survey. 23 records from Frohlinder Mühlenbach (Dortmund-Kirchlinde). 523 records from Fungi Collection. 3 records from Species status of Colias misti (Pieridae: Coliadinae) from the Arequipa region South Peru, and a description of its new subspecies, from Cotahuasi canyon South-Central Peru. 5 records from Oribatids from Switzerland II. (Acari: Oribatida). (Acarologica Genavensia XC). 9 records from Review of Pennella Oken, 1816 (Copepoda: Pennellidae) with a description of Pennella benzi sp. nov., a parasite of Escolar, Lepidocybium flavobrunneum (Pisces) in the northwest Atlantic Ocean. 1309 records from California State University, Long Beach Birds. 55 records from Naturmiljø Bergensbanen 2015 (project number 616033). 1314 records from Plant niche rather than soil or species shapes the microbiota. 15 records from Données espèces - Expertise IPE 70. 12 records from Two new genera and three new subterranean species of Hydrobiidae (Caenogastropoda: Truncatelloidea) from Tunisia. 22 records from Ostracoda abundance of Hole 24-238. 365 records from Données de la naturaliste Lemoine Delphine provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from Marine metagenome ICM_AWP. 66219 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 4 records from A new species of the flower bug genus Orius Wolff (Hemiptera: Anthocoridae) cryptically inhabiting Hibiscus tiliaceus L. (Malvaceae). 43 records from Steinbruch Mainz-Weisenau, 2. Jahr. 4860 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Lichens. 5175 records from NE Scotland other invertebrate records 1800-2010. 11904 records from NE AVH data. 11 records from Birdrace-Di_Bi_Di_Birder-Wesel. 12 records from Caddisflies (Insecta: Trichoptera) from Santa Catarina Lachatao, Oaxaca, México: New species, new geographical records, and checklist. 417 records from Biodiversidad selecta de los humedales de Laguna de Términos - Pantanos de Centla (Plantas). 4 records from (Table 1.2.1.1) Abundance of sympagic meiofauna of sea-ice core PS69/549-2. 353 records from Base de datos de la flora de la Reserva de la Biosfera Chamela-Cuixmala, Jalisco, México. 19 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz. 81 records from Données opportunistes sur les odonates. 64 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 13 records from Schulgelände (Wetter). 53 records from Deponie Klausdorf. 36 records from Review of the millipede family Haplodesmidae Cook, 1895, with descriptions of some new or poorly-known species (Diplopoda, Polydesmida). 15 records from Ameroculodes miltoni, a new species of estuarine amphipod (Crustacea: Malacostraca: Peracarida: Oedicerotidae) from the southeastern United States. 232 records from Census of animals species through Benin from 2011 to 2019. 5159 records from Données Entomologiques A. HORELLOU 1988-2018. 10 records from Kuhwiese Beerentaltrift (Hamburg/ Harburg). 3782 records from University of Jena, Herbarium Haussknecht - Herbarium JE. 88 records from Données du/de la naturaliste Cousin Richard provenant de la base de donnée du SINP Île-de-France CETTIA. 130 records from 2019_NSMK_PL. 128 records from Establecimiento de un área protegida en el Alto y Bajo Calima, área clave de biodiversidad en el Valle del Cauca, Colombia. 154 records from Erlengraben/Lipp-Tal (Östringen). 3332 records from Floristische Kartierung Österreichs - Mapping the Flora of Austria. 28 records from CSIC-Real Jardín Botánico-Colección de Algas (MA-Algae). 1536 records from Records of Halicarcinus planatus at sub-Antarctic regions. 4 records from Observations de Coléoptères saproxyliques de Frédéric LACOSTE. 958 records from Colección de Alismatales, Apiales, Aquifoliales, Arecales y Asparagales del Museo Botánico CORD - IMBIV. 259 records from Herbier National de Guinée (HNG). 2 records from A new species of the genus Diogenes Dana, 1851 (Crustacea: Decapoda: Anomura: Diogenidae) from Gujarat, northwestern India. 4 records from Overview of Niphargidae (Crustacea: Amphipoda) in Belgium: distribution, taxonomic notes and conservation issues. 1 records from NZCS Paloemeu River - Grensgebergte Mountains Expedition Conservation International RAP 2012. 1461 records from Population research on small rodents (Rodentia) and screws (Soridae) in Steinkjer Municipality – Norway; 2018 - 2019 based on systematic catches with ordinary mouse traps in traplines. 152 records from EDIT - ATBI in Gemer area (Slovakia). 22137 records from Global compendium of Aedes albopictus occurrence. 101 records from Colección de Herpetología de la Universidad del Quindío (HERPETOS-UQ). 173 records from BioGIS - Reptiles - HUJ collections. 18 records from Teich Berlin Wuhlheide. 5 records from An overview of the genus Plesionika Bate, 1888 (Decapoda, Caridea, Pandalidae) in Asian waters. 32 records from AKG-Gelände (Bensheim). 181954 records from Flora Atlas N.T.. 71 records from Herbaceous and arboreous plants list on the Komaba Campus of University of Tokyo, Japan. 176 records from Herbario COFC de la Universidad de Córdoba: colección histórica. 54 records from Redescription of Cletocamptus albuquerquensis and C. dominicanus (Harpacticoida: Canthocamptidae incertae sedis), and description of two new species from the US Virgin Islands and Bonaire. 1519 records from WOLL AVH data. 244 records from Respaldo de las colecciones de tejidos del Museo de Zoología, Departamento de Biología Evolutiva, Facultad de Ciencias, UNAM (Aves). 59 records from Naturschutzgebiet Heiliger Hain (Wahrenholz). 84 records from Ostracoda abundance of Hole 48-403. 184 records from Late Cretaceous and Cainozoic bathyal Ostracoda of DSDP Site 62-463 in the Central Pacific (Fig. 3). 364 records from New Mexico Museum of Natural History and Science (NMMNH&S) Herbarium specimens (Arctos). 446 records from Données de la structure SNPN - Société Nationale de Protection de la nature provenant de la base de donnée du SINP Île-de-France CETTIA. 9821 records from Atomariine Beetle (Coleoptera) records for Britain and Ireland to 1992. 9 records from Données de la Réserve Naturelle Nationale de Saint-Quentin-en-Yvelines provenant de la base de donnée du SINP Île-de-France CETTIA. 23 records from Colección de Peces del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P). 332 records from Alterra (NL) - Entomofauna inventory in arable fields Hoeksche Waard. 24 records from Données du/de la naturaliste jourdan christian provenant de la base de donnée du SINP Île-de-France CETTIA. 375 records from Analysis of macrobenthos in the Southern Bight of the North Sea (1971-1972). 13 records from Caddisflies (Insecta: Trichoptera) from Maranhão State, Northeast Region, Brazil: A new species, checklist, and new geographical records. 48 records from Colección de Referencia de Macroinvertebrados Bentónicos del Museo de Ciencias de la Universidad El Bosque. 1 records from Interstitial and parasitic Platyhelminthes from the coast of the Seychelles in 1992 and 1993. 449 records from HUEMG herbarium - Universidade do Estado de Minas Gerais - Campus Carangola - Herbário Virtual REFLORA. 1749 records from Liste des insectes associés au Vitellaria paradoxa C. E Gaertner, au Centre et au Nord du Bénin. 1 records from Descriptions of new Genera and Species of Odonata in the Collection of the British Museum, chiefly from Africa.. 7 records from Ostracoda abundance of Hole 32-306. 57 records from Colección base (BGVPA) del Banco de germoplasma del Jardín Botánico Atlántico de Gijón. 33 records from Lebensraum Gesamtschule (Langerwehe). 283 records from Antarctic Amphipoda. 6 records from Two new species of the genus Microlysias (Crustacea, Amphipoda, Tryphosidae) from Korean Waters. 1451 records from Proyecto interno ejecutado por la CONABIO: Sistema de información sobre Bosque Mesófilo de Montaña de México para apoyo en programas de restauración (Fase 1). 14678 records from Butterflies of Ireland. 13 records from Freshwater amphipods from Barrow Island, Western Australia. 25 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 6 records from Two remarkable new species of oribatid mites (Acari: Oribatida) from Acacia litter of Kerala, India. 6 records from Redefinition of Cornexcisia Fan & Kano, 2000 (Diptera: Sarcophagidae), with the first description of the female of Sarcophaga kurahashii (Shinonaga & Tumrasvin, 1979). 593 records from Inventaire des espèces végétales du sous bois des plantations de Teck de la forêt naturelle de la Lama. 1 records from New state records of lady beetles (Coleoptera: Coccinellidae: Coccinellinae) from Missouri and Mississippi, USA. 16 records from Dorfrand Mauderode. 113 records from SCFS - Sagehen Herbarium. 73 records from SuLaMa reptile survey I 2012. 61 records from Shrews of Poland. 73 records from Données du/de la naturaliste Beutin Sabine provenant de la base de donnée du SINP Île-de-France CETTIA. 10 records from Morphological systematics of kingsnakes, Lampropeltis getula complex (Serpentes: Colubridae), in the eastern United States. 5513 records from Données naturalistes de Pascal Dupont. 5725 records from Pautas para el manejo y ordenamiento de una pesquería multiespecífica de crustáceos en un área natural protegida: El caso de la Ría Celestún, Yucatán. 808 records from Woodmeadow Invertebrate Survey 2019. 4478 records from K-State Museum of Entomological and Prairie Arthropod Research. 1 records from suivi du site Natura 2000 Carrière Saint Nicolas. 5 records from New distributional records and life stage description of Caenis species (Ephemeroptera: Caenidae) from Brazil. 27 records from Microzooplankton abundance measured on water bottle samples at station PS58/061-1. 9640 records from TPWD HARC Texas Coastal Fisheries Corpus Christi Bay Bag Seine. 1 records from Inventaire des sangsues - détermination prélèvements de bureau d'études (qualité de l'eau) - Subvention UMS Patrinat. 98 records from Bird specimens of Bihoro Museum. 39 records from Registros de macroinvertebrados acuáticos en un bosque seco del municipio de Honda. 2 records from Faunal assemblage of sediment core GS7603-13. 119 records from New Staphylinidae (Coleoptera) records with new collection data from New Brunswick, Canada. I. Aleocharinae. 7 records from (Table 2.2.2.1) Integrated abundance of sympagic meiofauna in sea-ice cores of Aurora Australis cruise SIPEX. 27 records from STELI 2015 Saint-Pée-sur-Nivelle (64) par l'association EcoGIS. 109 records from Monitoreo de la abundancia, riqueza y biodiversidad de aves del Santuario de Flora y Fauna Galeras en 2019. 6 records from UNIVATES - Coleção de Ornitologia do Museu de Ciências Naturais da Universidade do Vale do Taquari - Univates (ZOUMCN-UNIVATES). 25460 records from Marine benthic dataset (version 1) commissioned by UKOOA. 212 records from HerpMapper. 4052 records from European Moth Nights. 28 records from Données du/de la naturaliste Roquinarc'h Océane provenant de la base de donnée du SINP Île-de-France CETTIA. 14 records from Occurrence data of Birds of the Upper Tana Basin, Kenya. 1740 records from Colección de Anfibios. 4 records from A new species of Bicoxidens Attems, 1928 (Diplopoda, Spirostreptida, Spirostreptidae) from northern Zimbabwe. 496 records from Zootaxa. 1260 records from Inventaire des Crustacés Décapodes de France métropolitaine. Données du compte CardObs 1113. 1001 records from Données du naturaliste MIGUET Pierre provenant de la base de donnée du SINP Île-de-France CETTIA. 2944 records from NBMB Herps. 376 records from Database on reference specimens for medicinal plants of the Fabaceae family, conserved at the CNARP herbarium. 7 records from Microbial diversity in the Benguela coastal upwelling system as derived from 16S rRNA sequencing and RNA Stable Isotope Probing (SIP). 9 records from A new species-group of Clubiona Latreille, 1804 and descriptions of four new species from Borneo (Araneae, Clubionidae). 38 records from Caracterización de vertebrados terrestres en el Cerro Guadalupe, municipio de Manzanares. 61 records from Aves de Caño Cristales, La Macarena, Meta. 108 records from Etude floristique de la forêt marécageuse de Lokoli au Bénin. 4 records from MfN - Micropaleontology. 447 records from Registro de vertebrados durante el fototrampeo del convenio 027 - 2014 CVC - Panthera. 82 records from SPC PROCFish/C Invertebrates Observations Wallis and Futuna 2005. 64 records from Umgebung der Gesamtschule Hamburg-Winterhude. 2245 records from Efectos del Cambio Ambiental en las comunidades de organismos de los ríos mediterráneos. 27 records from Distribution patterns of subtidal macrobenthos in the Tsitsikamma National Park. 166 records from BUND - Dassower See (Lübeck/Dassow). 5617 records from Données naturalistes de Monsieur François FOURNIER. 41 records from Birds and plant species near Petushki town (Vladimir region). 222 records from Fungal specimens of Faculty of Agriculture and Life Science, Hirosaki University. 80 records from Revues diverses et littérature grise.. 5631 records from Naturhistorisches Museum Mainz, Feldbeobachtungsdaten Pflanzen. 1 records from Jeu de données convention FEGVE-SPN (numéro 2). 15 records from Three new species of the genus Rhyzobius Stephens, 1829 from New Guinea (Coleoptera: Coccinellidae: Coccidulini). 417 records from TPWD HARC Texas Coastal Fisheries Sabine Lake Gill Net. 10 records from DREAL_PACA_-_N2000_-_Pays_Provence_Verte_2017_12_18. 73 records from Expedición Providencia I - INVEMAR. 161 records from Creación de un área protegida pública local en los municipios de Roldanillo, La Unión y Toro.. 4 records from Lindesnes. 4 records from Catalogue of distribution of lizards (Reptilia: Squamata) from the Brazilian Amazonia. III. Anguidae, Scincidae, Teiidae. 6235 records from Insect specimen database of Atsugi City Museum. 5 records from Bulletin d'informations de l'Association française de Lichénologie. 168 records from Nematoda of Costa Rica (INBio). 14 records from A checklist of seed-beetles (Coleoptera: Chrysomelidae: Bruchinae) from Iran. 157 records from A Revision of the Nearctic Predaceous Midges in the Bezzia (Bezzia) pulverea complex (Diptera: Ceratopogonidae). 14 records from Tejidos de especimenes colectados en la ventana de biodiversidad Río Guamués, corregimiento El Encano, Municipio de Pasto, Nariño, Colombia. 33 records from Revision of the family Acidopsidae Števčić, 2005, and the systematic position of Typhlocarcinodes Alcock, 1900, Caecopilumnus Borradaile, 1902, and Raoulia Ng, 1987, with descriptions of two new genera and five new species (Crustacea: Brachyura: Goneplacoidea). 80 records from Occurrence Data of Small Carnivores (Mammalia, Carnivora) in the National Museums of Kenya Zoology Collection. 237 records from Capercaillie national surveys. 45 records from La familia Asteraceae en México. Fase VI. 477 records from Regroupement de données Odonates et Lepidotères. 3704 records from WTSWW Data: All Taxa (West Wales). 498 records from EDP Foz Tua Nocturnal Birds - Ecological Monitoring Program [2011-2017]. 1 records from Pollen record of profile 3TZ. 524 records from Fichas diagnósticas para 10 especies de anfibios y reptiles mexicanos. 9 records from Three new species of the millipede genus Hyleoglomeris Verhoeff, 1910 from the Aegean region of Greece (Diplopoda, Glomerida, Glomeridae). 40761 records from Cartografía de vegetación a escala de detalle 1:10.000 de la masa forestal de Andalucía. 22 records from Données espèces - Expertise IPE 10. 170 records from Mycological collection of the National Museum. 42 records from "Ahrschleife bei Altenahr". 1 records from A new species of Leuctra from Turkey, and notes on Anatolian Rhabdiopteryx (Plecoptera: Leuctridae & Taeniopterygidae). 183 records from Distributional data on high altitude endemic taxa of vascular plants from western Balkans. 52544 records from South Australian Museum Australia provider for OZCAM. 9 records from Five new species of Candoninae (Crustacea, Ostracoda) from the alluvial valley of the Upper Paraná River (Brazil, South America). 1 records from Occurrence of mammalia relicts at site Stockton-on-Tees. 6 records from Brock University Herbarium (BU). 8996 records from SIO Benthic Invertebrate Collection. 146 records from Whicher Scarp Flora Survey. 2207 records from DASSH Data Archive Centre volunteer survey data. 73589 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Aves Reproductoras. 103 records from Biodiversidad vegetal de la parte alta oeste de la cuenca del Chuviscar, Chihuahua. 28 records from (Abb. 8 bot) Pollen profile Radauerborn, Harz. 26 records from Unter hellen Zinnen und finsteren Grotten. 14 records from Insectos de la expedición en el páramo de Ocetá, Boyacá - Proyecto Boyacá BIO. 124 records from Observaciones de Aves asociadas a investigaciones de la Univerisdad ICESI en el periodo 2014-2019. 28 records from Apoyo a las colecciones biológicas de la Facultad de Ciencias de la UNAM: Fase 1 (Coleóptera). 11 records from BIRDRACE Immerwiederhopf. 38 records from An annotated taxonomic checklist of the Neotropical Gracillariidae (Lepidoptera) with links to the information on host plants and parasitoids. 4 records from Description Of Six New Species Of Spiders Of The Genera Lathys (Family: Dictynidae), Marpissa (Family: Salticidae), Misumenoides (Family: Thomisidae), Agroeca (Family: Clubionidae), Gnaphosa (Family: Gnaphosidae) And Flanona (Family: Lycosidae) - From India. 856 records from Modernisation des ZNIEFF du PnrL. 5 records from Dombeya sevathianii (Malvaceae): A new critically endangered species endemic to Mauritius (Indian Ocean). 17 records from Caracterización de Reptiles de las lagunas del municipio del Medio Baudó. 49 records from Muestreos y recolectas de flora endémica y casi-endémica de matorral costero y chaparral de la zona mediterránea Baja California, México. 2 records from Occurrence of mammalia relicts at site Niederlehme. 32 records from Grand Voyeux - Suivis scientifiques. 3 records from UWIZM Cnidarians. 45 records from Ectopsocidae (Psocodea: ‘ Psocoptera’) from Valle del Cauca and NNP Gorgona, Colombia. 42 records from Colección Taxonómica Nacional de Insectos “Luis María Murillo” (CTNI). 70 records from Coastal and Marine Species Database. 13208 records from NEON Biorepository Carabid Collection (Pinned Vouchers). 146 records from Convention Fédération française de golf - MNHN 2016-2019.. 1 records from The order Tethyida (Porifera) in California: taxonomy, systematics, and the first member of the family Hemiasterellidae in the Eastern Pacific. 4409 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Invertebrates National Collection (MACNIn). 17535 records from Tasmanian Museum and Art Gallery provider for OZCAM. 224 records from TTRS Mammals. 2 records from Chapter 7: Linnaean Plant Names and their Types (part Z). 8 records from Weidegebiete in der Selzrenaturierung. 49 records from Occurrence of mammalia relicts at site Veternica. 8 records from MVZ Herp Observations (Arctos). 2 records from Occurrence of mammalia relicts at site Großes Schulerloch. 3 records from A new species of Macrothrix (Crustacea, Branchiopoda, Macrothricidae) from the Neotropics with description of the marthae-group. 57 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 1 records from New and little known Orthoptera (Ensifera and Caelifera) from the Ñambí River Natural Reserve, Nariño, Colombia. 1284 records from Plan Aménagement et de Gestion Simplifié (PAGS) des forêts galeries des départements de l'Ouémé-Plateau. Data mobilized in the framework of a JRS Biodiversity Foundation project in Benin. 15 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 143 (N.S) n° 36 (1), 2008 - Données faune. 117 records from Agromyzidae (Diptera: Schizophora) in the state of Pará: new species and new records in Brazil. 910 records from Aves Acuáticas de las sabanas inundables del Meta y Casanare. 257 records from Colección Entomológica CDMB. 16 records from NZCS Invertebrates New Collection After 1987. 1 records from A new species of the subgenus Troginus Mulsant et Rey 1878 (Coleoptera: Staphylinidae: Oxytelinae: Carpelimus) from Borneo. 26 records from Données naturalistes d'Olivier LAURENT. 94 records from Uncultured eukaryotes Targeted Locus (Loci). 15922 records from Restauración y conservación de Isla Guadalupe. 5134 records from Lepidoptera (Specimens NRM). 41 records from Mollusca specimens of Wakayama Prefectural Museum of Natural History. 15 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Caprimulgidae. 16 records from Colección nacional de palmas de Colombia - JBQ. 2650 records from Biodiversidad asociada al gasoducto Paiva-Caracolí. 5 records from ROC RSPB Farmland Species Survey Dataset. 9 records from Warnowtal (Rostock). 12 records from Site Condition Monitoring of dragonflies on Loch aí Mhuilinn SSSI potential extension - 2016. 5 records from TWO NEW SPECIES OF ORIPODOIDEA (ACARI: ORIBATIDA) FROM VIETNAM Sergey G. E and Alexander E. A. 205 records from Wild boar sightings held by Andy Riches. 43 records from Chronicle of Nature - Phenology of Birds of FSBI United Administration of the Lazovsky State Reserve and National Park Zov Tigra. 79 records from Chronicle of Nature - Phenology of Insects of Baikalsky State Nature Biosphere Reserve. 279 records from Las comunidades de myxomicetes de selva baja caducifolia. 1 records from Wuhle - Brücke / B1. 31 records from A new western Atlantic snapping shrimp of the Alpheus macrocheles group (Caridea, Alpheidae) revealed by morphological, molecular and color data. 4671 records from Marie-Victorin Herbarium (MT) - Bryophytes. 89 records from Caracterización bionómica de zonas de dragado y de afección de obras en la Ría de Ferrol. 575 records from Collection of saproxylic and xylobiont Beetles. 8 records from Compost microbe establishment and growth in agricultural soils. 3 records from Composición florística y estructura de tres parcelas permanentes en diferentes estados sucesionales en transición de bosques húmedos tropicales con bosques secos tropicales del municipio de Lebrija, Santander (Primer censo). 40019 records from National Benthic Inventory. 943988 records from The Danish Environmental Portal, species and habitats-database "Danmarks Miljøportals Naturdatabase". 76 records from EDP Foz-Tua: Nocturnal Birds - Complementary Studies [2010]. 30 records from Phenological Center - Mushrooms (Karelia). 60 records from Caracterización de vegetación para el establecimiento de límites funcionales de humedales: Ciénaga de la Virgen, Ciénaga Zapatosa y Complejo Hato Corozal - Paz de Ariporo. 3 records from Occurrence of mammalia relicts at site Meiendorf. 9 records from Occurrence of mammalia relicts at site Laugerie-Haut e-Est. 9 records from BIRDRACE Die Wendehälse. 9 records from The genus Jeekelosoma Mauriès, 1985 - Moroccan cave millipedes (Diplopoda, Polydesmida, Paradoxosomatidae). 75 records from Review of genus Hydropsyche Pictet 1834 (Insecta: Trichoptera: Hydropsychidae) from India. 3 records from Exotic speciments butterflies at Museum Zoologi Bogor, Indonesia. 6 records from Thoridae (Crustacea: Decapoda) can penetrate the Abyss: a new species of Lebbeus from the Sea of Okhotsk, representing the deepest record of the family. 3233 records from Wild Bee Specimens from Blueberry and Raspberry Farms in the Champlain Valley, Vermont, USA. 506 records from Données de type contact en Guadeloupe. 845 records from Intermountain Herbarium (fungi, not lichens), Utah State University. 1 records from First records of the jewel beetles Chrysobothris desmaresti (Laporte & Gory, 1836) and Hiperantha stempelmanni Berg, 1889 (Coleoptera: Buprestidae) in Bolivia. 20025 records from Finnish Floristic Database (Vascular plant data of Kevo Subarctic Research Institute). 4454 records from HUCP herbarium - Pontífica Universidade Católica do Paraná PUC - Herbário Virtual Reflora. 1476 records from Canadian Museum of Nature Palynology Collection. 1830 records from Flora superior del Bosque Seco Tropical presente en 10 parcelas ubicadas en el Valle del Cauca. 2 records from A new species of Fannia (Diptera, Fanniidae) from Yunnan, China. 323 records from Herpetofauna de la región del Mar Muerto, Oaxaca-Chiapas. 10 records from Revision of Afrotropical species of the Philonthus peripateticus species group (Coleoptera: Staphylinidae: Philonthina). 20287 records from Phytochorologie des départements français. 492 records from A grid-based database on vascular plant distribution in Samoylovsky District of Saratov Oblast, Russia. 1087 records from IRKU Herbarium: collections of vascular plants. 196 records from Sammlung Eggers Westindien Herbarium Hamburgense HBG. 10 records from "Natur macht Schule 2" Natur im Wohngebiet Gorndorf. 1 records from New records of Solenocera barunajaya Crosnier, 1994 and Solenocera rathbuni Ramadan, 1938 (Crustacea: Decapoda: Penaeoidea) from the southwest coast of India. 3 records from DSMZ Bacteria. 8 records from Galls on Beech Trees in Hainich, 2008. 304 records from SEFSC Mid-Atlantic Tursiops Survey, 1995 3. 1422 records from Atlas des Poissons et Crustacés d'eau douce de Guadeloupe. 79769 records from CAS Entomology (ENT). 418 records from Inventario multitaxonómico del ANP Médanos de Samalayuca. 48827 records from Carnet B Lorraine. 105 records from Naturalis Biodiversity Center (NL) - Pisces. 7 records from Ecosystems of the sandstone region incl. sand-belt (SE of Melb.). 23 records from Eine neue Art der Gattung Quedius STEPHENS aus Syrien (Coleoptera, Staphylinidae, Staphylininae, Staphylinini, Quediina. 53 records from Myxomycetes collection of the University of Eastern Finland. 44 records from Black fungus gnats (Diptera: Sciaridae) found in association with cultivated plants and mushrooms in Australia, with notes on cosmopolitan pest species and biosecurity interceptions. 8183 records from Données du/de la naturaliste Bottinelli Julien provenant de la base de donnée du SINP Île-de-France CETTIA. 56672 records from Seasearch Marine Surveys in England. 20 records from New data on the fauna of China, part I: the taxonomy of the millipede family Julidae (Diplopoda). 96 records from Annales de la Société Linnéenne de Maine-et-Loire. 1 records from Arthropoden aus südostalpinen Höhlen.. 4 records from A review of the genus Coccoglypta Pilsbry, 1895 (Gastropoda: Pulmonata: Camaenidae). 27 records from Tejidos de la expedición en el páramo de Rabanal, Boyacá - Proyecto Boyacá BIO. 286 records from Chronicle of Nature - Phenology of Insects of Pechoro-Ilych State Nature Reserve. 57 records from Swiss Occurrence Records of Native Species of Various Faunal Groups. 5125 records from Collection Trichoptera - SMF. 1558 records from Insectes Hétéroptères Mirides de France. 33 records from Integrierte Gesamtschule Flensburg Wiemoosgraben. 193 records from Données du naturaliste ROCHAT Didier provenant de la base de donnée du SINP Île-de-France CETTIA. 45 records from The pholcid spiders of Sri Lanka (Araneae: Pholcidae). 1 records from A review of the Stenetriidae (Crustacea: Isopoda: Asellota). 1 records from Fossil Sciaroidea (Diptera) in Cretaceous Ambers, Exclusive of Cecidomyiidae, Sciaridae, and Keroplatidae. 74 records from Occurrence of mammalia relicts at site Raj Cave. 354 records from Programme ACT : Répartition Caille des blés 2000 - 2004 Coordonnées GPS Lambert 93. 3 records from Four new species records of Antennoseius and Anystipalpus (Acari: Mesostigmata: Ascidae) phoretic on Carabidae beetles from France. 781 records from Chronicle of Nature - Phenology of Plants of State Nature Reserve Olekminsky. 10 records from Taxonomic applications of the esophageal flapper valve in the Genus Neonesidea (Bairdioidea, Podocopida, Ostracoda), including descriptions of new and poorly known species from the Caribbean and Gulf of Mexico. 139 records from Pollen analysis of sediment core GeoB6518-1. 117 records from First record to Brazil of one genera and seven species of Psychodidae (Diptera) with further new records for 10 countries on the Neotropics. 28943 records from BLS Mapping Scheme dataset, 1750-2009. 12165 records from Arizona State University Hasbrouck Insect Collection. 284 records from Chronicle of Nature - Phenology of Plants of Kronotsky Federal Nature Biosphere Reserve. 874 records from Fonoteca Zoológica, Museo Nacional de Ciencias Naturales, Madrid: FZ_AMPHIBIA. 63364 records from CCAMLR historic KRILL. 413 records from Collection Strepsiptera SMF. 583 records from Ostracoda in sediment core PS51/159-10. 342 records from NHMD Amber Collection. 81 records from Données du naturaliste DESCHATRE Thierry provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from Review of genera of Sciomyzidae (Diptera: Acalyptratae) from China, with new records, synonyms, and notes on distribution. 266 records from Mushroom (KIDR-MR). 2 records from Avifauna de los bosques húmedos y remanentes de Tierralta - Córdoba, 2011. 279442 records from Liste des espèces de la faune sauvage de la base de données naturalistes Faune-France 2018.. 1 records from Genetic and morphological evidence for cryptic species in Macrobrachium australe and resurrection of M. ustulatum (Crustacea, Palaemonidae). 58 records from Point Count Data for TIDE's Private Land (Kern), Belize 2009-2013. 797 records from NEON Biorepository Mammal Collection (Vouchers [Standard Sampling]). 25 records from Colección Ornitológica del Museo de Historia Natural de la Universidad de la Amazonia. 272 records from Colección de Boraginales y Brassicaless del Museo Botánico CORD - IMBIV. 3 records from Two new and one known marine water mite (Acari: Hydrachnidia: Pontarachnidae) from South-East Africa. 399 records from Revision of the family Chasmocarcinidae Serène, 1964 (Crustacea, Brachyura, Goneplacoidea). 5 records from A new species of Paraproto (Crustacea: Amphipoda) from southern New SouthWales, Australia. 5005 records from Sepsidae (Diptera) records from Britain and Ireland to 1985. 3 records from Two new species of Leptarma (Decapoda, Brachyura, Sesarmidae) from the Western Indian Ocean with notes on their phylogeny. 698 records from Collembola of Prioksko-Terrasny Nature Reserve: multi-scale spatial distribution analysis in pine forests. 61 records from The caddisfly genus Protoptila in Costa Rica (Trichoptera: Glossosomatidae). 16206 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 5 records from Etude d'état initial de la biodiversité dans le cadre des EIES sur les plateaux situés dans la zone sud (Pompo) de la concession minière de Guinea Alumina Corporation(GAC) dans la region de Boké (CESP2016-022). 154 records from Modelación de la distribución potencial del género Bursera (Burseraceae) en México. 10734 records from FLOR - Herbário do Departamento de Botânica da Universidade Federal de Santa Catarina. 405 records from Alterra (NL) - Microarthropods inventory in Dune vegetation. 22 records from Site Condition Monitoring of dragonflies on Loch aí Mhuilinn NNR - 2002. 252 records from University of Sindh Jamshoro Herbarium. 3 records from Occurrence of mammalia relicts at site la Grotte des Eglises. 17 records from Einen Tag lang Forscher sein - Die 5c der Erich-Kästner-Schule erforscht das Bachemer Wiesental. 256 records from Inventaire des pelouses calcicoles du PNR du Marais Poitevin 2017. 34 records from Densidad poblacional para fauna medida por medio de cámaras trampa en los Valores Objeto de Conservación (VOC) del territorial Andes Occidentales. 30 records from (Appendix) Foraminifer abundance of a volcaniclastic interval from ODP Hole 197-1206A. 3 records from New Galumnoidea (Acari, Oribatida) from Hanoi (Northern Vietnam). 37 records from Registros biológicos asociados al monitoreo de la diversidad de escarabajos en paisajes ganaderos silvopastoriles - Unillanos 2019. 1479 records from Saproxylic and herbivorous beetle species in old near-natural and old managed forests in south-eastern Norway. 2 records from Faunal assemblage of sediment core TR149-32. 2 records from MFS-Plantulas - Herbário Profª. Drª. Marlene Freitas da Silva - Coleção de Plântulas. 787 records from Programme ACT : Répartition Pie bavarde 2009 - 2013 Coordonnées GPS Lambert 93. 34 records from Tree-dwelling ant survey (Hymenoptera, Formicidae) in Mitaraka, French Guiana. 4 records from Two deep-sea decapod crustaceans collected off eastern Hokkaido, Japan: Sclerocrangon rex n. sp. (Caridea: Crangonidae) and Munidopsis verrilli Benedict, 1902 (Anomura: Munidopsidae). 16 records from On three new species of Elpidium Müller, 1880 and the re-description of Elpidium laesslei (Tressler, 1956) from Jamaica (Ostracoda: Podocopida: Limnocytheridae). 27 records from Borstgrasrasen um die Burg Baldenau im Oberen Dhrontal. 29 records from Swedish Malaise Trap Project (SMTP) - Pimplinae. 389 records from HJ herbarium - Universidade Federal de Goiás - Unidade Jataí - Herbário Virtual REFLORA. 2 records from Two new scale insect species (Hemiptera: Coccomorpha: Acanthococcidae and Pseudococcidae) and a new country record from protected areas in Iran. 7 records from Bases de datos de plantas, insectos, reptiles, anfibios, aves y mamíferos del “Arroyo la Junta, Una joya de biodiversidad en la Reserva de la Biosfera Sierra La Laguna” (Reptiles y anfibios). 98 records from BID-Malawi-Geometridae-Biodiversity-Data. 105 records from Inventaire et suivi odonate/Fadet des laîches des sites Natura2000 ‘Zones humides de l’étang de Léon’ et ‘Zones humides de l’arrière dune du Marensin’. 190 records from The freshwater shrimp family Euryrhynchidae Holthuis, 1950 (Crustacea: Decapoda: Caridea) revisited, with a taxonomic revision of the genus Euryrhynchus Miers, 1878. 11 records from Schulgelände Lise Meitner Realschule (Paderborn). 14 records from Birdrace-Uhulogen-Lippe. 8927 records from Collection Aves (bird skins) SMF. 4 records from Revision of the stygobiont gastropod genera Plagigeyeria Tomlin, 1930 and Travunijana Grego & Glöer, 2019 (Mollusca; Gastropoda; Moitessieriidae and Hydrobiidae) in Hercegovina and adjacent regions. 17 records from Feral Pigs - Sightings and Cull records - 2018-2019. 1 records from Lanayrella, a new Acteonidae genus (Gastropoda, Heterobranchia) from Tierra del Fuego. 81 records from Computarización de la Colección de helmintos parásitos de peces del estado de Tabasco. 17 records from DNA barcoding and morphological studies confirm the occurrence of three Atarbolana (Crustacea: Isopoda: Cirolanidae) species along the coastal zone of the Persian Gulf and Gulf of Oman. 48 records from Swedish Malaise Trap Project (SMTP) - Odonata. 17 records from Birdrace-SpeedBirder-Zwickauer_Land. 14 records from Birdrace-Die_Vogelscheuchen-Herford. 117407 records from Données Observatoire des Papillons des Jardins. 2933 records from JOI - Herbário Joinvillea. 1036 records from BioGIS - Mammals - SPNI. 32 records from Carnarvon Basin wetland survey. 66 records from Chronicle of Nature - Phenology of Birds of Darwin Nature Biosphere Reserve. 75 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Invertebrados. 5706 records from Inventaire et suivis d'espèces dans le Parc national des Cévennes. 88670 records from SEWBReC Birds (South East Wales). 44 records from Luderbusch. 10 records from Teich im Wald zwischen Böblingen und Schönaich. 92 records from Monitoreo de aves por medio de puntos de conteo en el Santuario de Flora y Fauna Galeras en 2016. 46 records from The Dragon-flies (Odonata) of Palestine, based primarily on collection made by Dr. P. A. Buxton, with Notes on the Species of the Adjacent Regions.. 1315 records from Lepidoptera of Mordovia State Nature Reserve. 8 records from A new species of freshwater crab of the genus Badistemon Yeo & Ng, 2007 (Decapoda: Brachyura: Potamidae: Potamiscinae) from Manipur State, India with the reassignment of Potamiscus pealianus (Wood-mason, 1871). 7 records from Visual Plants (144.41.33.158) - Plants from Costa Rica, illustrations by Teresa Barantes Lobo. 1017 records from Agroforestry species in Parkia biglobosa's parklands in Northern Benin. 12601 records from Isle of Man wildlife records from 01/01/2000 to 13/02/2017. 239 records from Colección Entomológica del Programa de Biología - Universidad de Caldas (CEBUC). 6396 records from MfN - Fossil vertebrates IV. 1 records from Fish Collection of Yokosuka City Museum. 96 records from Malawi-Cicindelidae-Biodiversity-Data. 22 records from The fishery ground near Alexandria. XVI. Cumacea, stomatopoda, leptostraca by Adolf Steuer (1938).Notes and Memoirs No 26.. 440 records from Global database of alien macrofungi. 38 records from A taxonomic review of the Korean species of the subgenus Datomicra Mulsant & Rey of the genus Atheta Thomson, with description of a new species (Coleoptera, Staphylinidae, Aleocharinae). 976 records from Dipterists Forum: Field Week 1981 (Kent). 901 records from MEXU/Flora de Oaxaca. 12848 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 205 records from Données araignées de Corse par Canard A., Rollard C., Villepoux O.. 3 records from Two new species of freshwater crabs from the highlands of northern Uganda, East Africa and a redescription of Potamonautes amalerensis (Rathbun, 1935) stat. rev. from Mount Kadam (Brachyura: Potamoidea: Potamonautidae). 1691 records from Eulachon migration bottom trawl surveys. 1921 records from Nonindigenous Aquatic Species (NAS) Database Non-freshwater Specimens. 488 records from Registros biológicos de flora para el desarrollo de acciones de evaluación, seguimiento y monitoreo en los elementos priorizados de la estructura ecológica principal del distrito capital. Bogotá D.C.. 8 records from Arizona State University Lois B. O'Brien Collection. 17 records from Occurrence of mammalia relicts at site Zigeunerfels. 442 records from Herbario virtual bosques secos de Colombia - Sección herbario TOLI (UT). 69 records from SNH Invertebrate Site Condition Monitoring 2013/14: Eastern Cairngorms SSSI. 92 records from Sammlung Ernst Ule sinenumero Herbarium Hamburgense HBG. 1874406 records from Pl@ntNet automatically identified occurrences. 20 records from Heavy minerals of sediment core PL94-64. 54 records from Amphibiens filet/Marbotte-Ronval 2013. 48420 records from Amphibiens et Reptiles de France (Enquête 2). 1811 records from Dolichopodidae of Portugal - dataset 2009-2018. 448 records from Inventario de la biota marina (cnidarios, poliquetos, moluscos, crustáceos, equinodermos y peces) del Santuario Islas e Islotes de Bahía Chamela, Jalisco, México. 1006 records from Ravensthorpe Range survey data. 31 records from SNH Invertebrate Site Condition Monitoring 2015: Blind Moss SSSI. 2860 records from Hemiptera (Heteroptera) collection of National Museum of Nature and Science. 4 records from artsprosjektet_48-15_naididae. 33 records from Wirbach-Taubental (Bad Blankenburg). 454 records from Données naturalistes d'Alain BERLY. 37424 records from Herps Specimens. 4483 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 26676 records from LSUMZ Birds Collection. 2 records from Two New Liocranid Species Records From Turkey (Araneae: Liocranidae). 7 records from Hache im Ellernbruch (Sudweyhe / Weyhe). 133 records from (Table 6) Ostracod assemblages of sediment core 9409. 155 records from Données opportunistes. 10 records from City of Edinburgh Natural Heritage Service - Harperrig Otter Survey. 194 records from Auburn University Museum of Natural History Mollusks. 1204 records from Yoann_BLANCHON_2017_12_18. 5 records from Two New Shallow-water Species of Agathotanais (Crustacea: Tanaidacea) from Japan. 53 records from Inventaire et regroupement de données Natura 2000. 6551 records from MSUM Ichthyology and Herpetology Collections. 21 records from Bird Specimens of The Cattle Museum. 1847 records from Genebank, National Institute of Agrobiological Sciences. 15 records from Banco de Germoplasma de la Universidad Rey Juan Carlos. 440 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Reptilia (ZUFMS-REP). 35 records from KARSTLANDSCHAFT SÜDHARZ - VOM GIPSABBAU BEDROHT (Grenzstreifen am Röseberg). 1 records from The fossil avifauna of the tar seeps Las Breas de San Felipe, Matanzas, Cuba. 3 records from New data on the Pterophoridae fauna of Liberia (Lepidoptera: Pterophoridae). 24 records from New insights into polyphyly of the harpacticoid genus Delavalia (Crustacea, Copepoda) through morphological and molecular study of an unprecedented diversity of sympatric species in a small South Korean bay. 994 records from ERBG AVH data. 45423 records from CABI Africa Invasive and Alien Species data. 7364 records from River Biologists' Database (EPA). 30 records from Selztal bei Friesenheim. 5307 records from Banded Iron Formation and Greenstone survey data. 243 records from Great Eastern Ranges - Slopes to Summit. 3813 records from UCM Mammal Collection (Arctos). 27 records from Hydroptilidae (Trichoptera) of Angola, a new genus, seven new species, and five new records. 2 records from New records and checklist of Chilocorini (Coleoptera: Coccinellidae) from China. 24693 records from Tiroler Landesmuseum Ferdinandeum. 5 records from Anfibios y reptiles de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 2506 records from Communautés adventices des systèmes cotonniers du nord Cameroun. 127 records from Pollen profile from a swamp at Seelohe, Fichtelgebirge, Germany. 4106 records from Données faune Nature 18 - 2017. 28017 records from Natural History Museum, Vienna - Herbarium W. 9 records from BIRDRACE Die Vriesischen Feigen-Vögel (VFV). 33 records from Mammals (GNHM-MM). 6784 records from Odonata records from RSPB Reserves 1970-2009. 11 records from Données du/de la naturaliste Dubois Yves provenant de la base de donnée du SINP Île-de-France CETTIA. 4941 records from University of Colorado, Museum of Natural History Herbarium Bryophyte Collection. 166 records from DREAL_PACA_-_N2000_-_Parc_Naturel_Régional_du_Verdon_2017_12_18. 21 records from Occurrence of mammalia relicts at site Bocksteinschmiede. 30 records from Feral Pigs - Sightings and Cull records - 2014-2015. 3 records from Anfibios presentes en el Cerro Jánano. 1 records from Lanlabeo duanensis, a new genus and species of labeonin fish (Teleostei: Cyprinidae) from southern China. 32 records from Chapter 7: Linnaean Plant Names and their Types (part V). 631 records from Odonata Specimens of Yamaguchi prefectural Yamaguchi Museum. 1391 records from Arthur Chapman Observations. 112 records from Cuxhavener Küstenheiden. 49687 records from University of Michigan Museum of Zoology, Division of Birds. 270 records from (Table 2) Fossil record of foraminifera and ostracoda from Muldsberg clay pit, north Germany. 255793 records from Hatikka Observation Database. 801 records from University of Wyoming Museum of Vertebrates (UWYMV) Bird Collection (Arctos). 75 records from Données naturalistes de Monsieur JOURDE Rémi. 94 records from Données naturalistes de AUNEAU Florent. 1 records from A new Atheta species from the West Caucasus and a redescription of A. brevapicalis (Coleoptera: Staphylinidae: Aleocharinae). 873 records from Programme ACT : Répartition Geai des chênes 2008 - 2012 Coordonnées GPS Lambert 93. 102 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Accipitridae. 13 records from uncultured marine picoeukaryote strain:Peuk_V4_NWP2 Raw sequence reads. 26222 records from inatura - Erlebnis Naturschau Dornbirn. 11 records from Occurrence of mammalia relicts at site l´Abri de Campalou. 97 records from Coleoptera identified from the Borax Works, Norman Road site, Bexley, London. 233 records from Birds (NHMK-BI). 1 records from Collection Graptolithina fossil SMF. 414 records from Colección de reptiles del Museo de Historia Natural de la Pontificia Universidad Javeriana. 89 records from Diatomeas (Bacillariophyceae) y dinoflageladas (Dinophyceae) frecuentes en el Pacífico mexicano (costa oeste de Baja California, Pacífico centro y sur). 12 records from Talitrid amphipods from India, East Africa and the Red Sea (Amphipoda, Senticaudata, Talitroidea, Talitridae). 505 records from Occurrence data of Swallowtail butterflies (Lepidoptera: Papilionidae) in the Zoology Museum of Makerere University. 6 records from New data on species diversity of Annelida (Oligochaeta, Hirudinea) in the Kharbey lakes system, Bolshezemelskaya tundra (Russia). 6 records from Occurrence data of mayflies available at the National Museums of Kenya's Natural History Collections, Invertebrates Zoology Section.. 4 records from Inventario Herpetológico Pauto M, La Primavera, Yopal, Casanare. 18 records from Megafauna of the UKSRL exploration contract area and eastern Clarion-Clipperton Zone in the Pacific Ocean: Annelida, Arthropoda, Bryozoa, Chordata, Ctenophora, Mollusca. 15 records from Zoo Frankfurt. 241 records from Propuesta para rescatar y conservar la paleobiota de la Cantera Tlayúa, en Tepexí de Rodríguez, Puebla: Fase II. 8 records from BIRDRACE Oostfreesland Bird-Lopers. 6 records from A new species of freshwater crab of the genus Phallangothelphusa Pretzmann, 1965, from the foothills of the Serranía Yariguíes of Colombia (Crustacea: Decapoda: Pseudothelphusidae). 17 records from Canada_BasinMegabenthos2002. 1 records from First description of the male of Glyphiulus formosus (Pocock, 1895) (Diplopoda Spirostreptida: Cambalopsidae) from China. 327 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2009. 32788 records from Database of invertebrates collected in Mongolia. 264604 records from Fungal Records Database of Britain and Ireland. 445 records from Vascular Plants Specimens of Ehime Prefectural Science Museum. 3941 records from Données bibliographiques et opportunistes Mammifères du Nord Pas-de-Calais issues du SIRF. 64099 records from Données de la flore d’Alsace (SBA). 7 records from Suivi naturaliste du Parc du Peuple de l'Herbe. 7 records from Pipunculidae (Diptera) from southern Iran, including two new species of the genus Tomosvaryella Aczél. 3 records from MSB Mammal Observations (Arctos). 460 records from (Appendix 1) DSDP Site 94-607 ostracode species census data. 30 records from Données du/de la naturaliste Goncalves Cristina provenant de la base de donnée du SINP Île-de-France CETTIA. 787 records from Species biodiversity transnational geo-database - IMPRECO Project. 70 records from Typotheca of the higher vascular plants stored in M.G. Popov Herbarium (NSK) at the Central Siberian botanical garden SB RAS. 194930 records from RSPB Big Garden Birdwatch winter sightings in the UK in 2009. 59 records from Occurrence of mammalia relicts at site Burghöhle Dietfurt. 4 records from Données naturalistes de Sophie COHEN. 51 records from Centre d'Estudis Avançats de Blanes. Macròfits Pirineu. 11120 records from Données Mammifères Midi-Pyrénées enregistrées dans BazNat - Lot 1. 2024 records from Wikiplantbase #Sicilia. 292 records from Paguroids (Decapoda: Anomura: Diogenidae and Paguridae) of the remote oceanic Archipelago Trindade and Martin Vaz, off southeast Brazil, with new records, description of three new species and zoogeographical notes. 1 records from Arthropoden aus südostalpinen Höhlen.. 5 records from Begonia henrilaportei Scherber. & J. Duruisseau (Begoniaceae), a new endemic species from the Masoala peninsula, Madagascar. 41 records from Database of Australasian Vertebrate Occurrences. 4 records from Review of the aquatic Hemiptera from Cephalonia, with a checklist for the Ionian Islands, Greece (Heteroptera: Gerromorpha, Nepomorpha, Leptopodomorpha). 83 records from bmhs_butterfly_collection. 68 records from Naturpark Kottenforst-Ville Sammelaktion 15.-19.6.. 167 records from Composición florística y estructura vegetal de una parcela permanente en un relicto de bosque seco tropical en el Caribe colombiano. 2 records from Abundance of benthos infauna at station POS128/2_284. 98 records from Phenological Center - Birds (Laplandskiy). 59 records from FPN-EH-AVES - Breeding Distribution of seabirds in Patagonia Argentina coast. 137 records from Caracterización de la vegetación en una zona delimitada en Cumbitara, La Llanada, Policarpa y Los Andes Sotomayor (Nariño), como insumo para la identificación de oportunidades de conservación para la recuperación de los servicios ecosistémicos de bosque seco. 29 records from Four Species of Dulichiidae (Crustacea: Amphipoda) from Japan, with the Description of a New Genus and Two New Species. 21 records from Inventaire faune flore de l'étang d'Abbecourt à Orgeval. 17 records from checklist-of-birds-of-zomba-mountain. 58535 records from Grasshopper and Cricket (Orthoptera) and related species records from Britain and Ireland to 2007. 2 records from Gewässeruntersuchung (Prien) mit Kl. 4b. 151 records from Plant of Folklore (KIDR-PL). 423 records from Programme ACT : Répartition Caille des blés 2008 - 2012 Coordonnées GPS Lambert 93. 1 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Glen Tarff SSSI. 40567 records from VegetWeb - Repositorium von Vegetationsaufnahmen. 40 records from Zooplancton de sistemas acuáticos artificiales y naturales de Colombia. 54 records from (Table 10) Eocene-Oligocene diatom biostratigraphy of ODP Hole 120-748B. 1112 records from Bird records for Argyll for the years 2002 and 2003. 105 records from SWECO. 837 records from Données naturalistes de Loïc SALAUN. 627 records from MfN - Fossil plants (Paleophytic). 2716 records from EDP Foz Tua: Terrestrial Birds (transects) - Ecological Monitoring Program [2009-2012]. 186087 records from Flore Franco-Belge. 3 records from A new genus and new species of Potamidea (Crustacea: Decapoda: Brachyura: Potamoidae), the first stygomorphic cave crab known from China and East Asia. 3 records from Insectos recolectados en trampas Malaise en el departamento de Vichada - Proyecto Colombia Bio. 12008 records from EAC - Herbário Prisco Bezerra. 497 records from East Ayrshire Species Database. 93 records from Euroants. 38 records from CNIN/Tipos Homoptera. 2893 records from Marine Biological Sample Database, JAMSTEC. 2 records from Insectos recolectados en trampas Malaise en el departamento de Antioquia - Proyecto Colombia Bio. 21521 records from Naturalis Biodiversity Center (NL) - Chelicerata and Myriapoda. 1 records from Ornitofauna de un Área Degradada por Actividad Minera en la Costa Caucana. 3 records from Hoplophthiracarus sidorchukae sp. nov. (Acari, Oribatida, Phthiracaridae) from the North Island, New Zealand. 417 records from Leif Richardson Vermont Bee Specimens. 1 records from The type specimens of bees (Hymenoptera, Apoidea) deposited in the Zoological Institute of the Russian Academy of Sciences, St. Petersburg. Contribution II. Family Halictidae, subfamilies Rophitinae, Nomiinae, and Nomioidinae. 9 records from PRA Sonneur à ventre jaune - étude de répartition. 18 records from A new genus and species of large-bodied caridean shrimp from the Crozet Islands, Southern Ocean (Crustacea, Decapoda, Lipkiidae) with a checklist of Antarctic and sub-Antarctic shrimps. 61 records from Données espèces - Expertise IQE 308. 63 records from Données espèces - Expertise IQE 95. 6 records from Inventaire Faune. 1575 records from MEXU/Tipos de plantas vasculares. 1528 records from Insect (ENHM-IN). 10 records from New state records and updated checklist of Aphodiini and Eupariini (Coleoptera: Scarabaeidae: Aphodiinae) from Mexico. 145 records from Results of the pollen analysis of the Dyanushka peat sediments K7/P2. 480 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2016. 50 records from Taxonomy of Anotylus nitidifrons group (Coleoptera: Staphylinidae: Oxytelinae) and five new species from China. 61 records from Packer Collection /Madagascar. 3 records from The Genus Pseudopomyza (Diptera: Nerioidea) in Tasmania, with Description of a New Species. 241 records from Données de Lépidoptères de Bruno DAUGET - Dépt de l'ALLIER (03). 59 records from Landschaftspflegehof (Berlin). 7 records from Four new species of giant pill-millipedes from Vietnam (Sphaerotheriida, Zephroniidae). 171 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 146 (N.S) n° 39 (4), 2011 - Données faune. 3 records from Oratosquilla septemdentata n. sp. (Crustacea: Stomatopoda: Squillidae), a new species of deep water stomatopod from Halmahera, Indonesia. 3 records from Bachpatenschaft Beeke. 2 records from Dr. Sultan Ahmad Herbarium. 14 records from BIRDRACE Hasenclevers Erben - NaBu-Bi-BirdRace-Open. 125 records from Données du/de la naturaliste Dodelin Benoît provenant de la base de donnée du SINP Île-de-France CETTIA. 8 records from Anfibios y reptiles del páramo de Sumapaz - Proyecto Colombia Bio. 966 records from TPWD HARC Texas Coastal Fisheries Upper Laguna Madre Gill Net. 7 records from The millipede family Striariidae Bollman, 1893: III. Four new species of Striaria Bollman, 1888 (Diplopoda, Chordeumatida, Striariidae) from Idaho, USA. 283 records from Gemeinde Sursee. 2 records from Two new species of Hyalella (Crustacea, Amphipoda, Hyalellidae) from state of Rio Grande do Sul, Southern Brazil. 715 records from City of Edinburgh Natural Heritage Service - Bavelaw Marsh Bird Hide Records. 398 records from Insect specimens of Omogo Mountain Museum. 11 records from Occurrence of mammalia relicts at site Nazeing. 57 records from Spatial repartition of Antiaris toxicaria Lesch., Ceiba pentandra (L) Gaert, Terminalia superba Engl. & Diels and Triplochyton scleroxylon K. Schum. in Niaouli, Bonou, Pobe forests (South-Benin). 1 records from marine metagenome. 39 records from Artenvielfalt auf den Elbwiesen (Dessau). 54 records from Coral Reef Evaluation and Monitoring Project Dry Tortugas 2008. 19 records from Modelaje de la distribución potencial de 10 especies de anfibios y reptiles en riesgo de extinción con escasos registros de presencia (ANONAU). 494 records from Chronicle of Nature - Phenology of Plants of Carpathian Biosphere Reserve. 1 records from Stabilisation of some names of European butterflies (Lepidoptera: Pieridae) in their prevailing usage. 14 records from Données de la naturaliste Clélie Granger. 154 records from Database on reference specimens for medicinal plants of the Rubiaceae family, conserved at the CNARP herbarium. 99 records from Flora y fauna asociada al hábitat del Manatí antillano en la Ciénaga de Paredes, Magdalena Medio Santandereano. 474 records from A revision of the minor species group in the millipede genus Nannaria Chamberlin, 1918 (Diplopoda, Polydesmida, Xystodesmidae). 189 records from SFSU - Vascular Plants of the Harry D. Thiers Herbarium at San Francisco State University. 12 records from Inventario de Mamíferos Mámbita. 365 records from Colección de Crustáceos del Instituto de Ciencias Naturales (ICN-MHN-Cr). 21860 records from Canadian Museum of Nature Mammal Collection. 33 records from Caracterización de la fauna reptiliana asociada a la cuenca del río Atrato, para el estudio de su navegabilidad, Quibdó - Chocó, 2012. 4 records from Feuchtwiese am Nationalpark-Haus Neuwerk. 50 records from Pollen and spore abundance of Hole 42-381. 51421 records from Estonian Nature Observations Database. 14 records from New and little known species of Halolaelaps (Acari: Mesostigmata: Halolaelapidae) from Ukraine. 14 records from Naturpark Sternberger Seenland. 8108 records from Botanical Museum, Copenhagen, Mycology Herbarium. 121 records from Inventaire des bois par espèce végétale de la forêt classée de Ziama en Guinée Forestière (BID-AF2015-0066-REG). 38 records from Birds (NMNO-BI). 5590 records from NCSM Mammalogy Collection. 16 records from Mesozooplankton - Crustacea from the South Adriatic Sea. 1 records from Les Gymnospermes de l'Herbier du Centre National de Floristique de Côte d'Ivoire. 1255 records from Aves del Parque Nacional Cumbres de Monterrey, Nuevo León, México. 28 records from Taxonomy of Paraplatyarthrus Javidkar and King (Isopoda: Oniscidea: Paraplatyarthridae) with description of five new species from Western Australia, and comments on Australian Trichorhina Budde-Lunde, 1908 (Platyarthridae). 6 records from DMNS Parasite Collection (Arctos). 155 records from Chronicle of Nature - Phenology of Insects of Kaniv Nature Reserve. 10 records from GEO-Tag mit der NAJU des Landkreises Ahrweiler am Bausenberg. 61 records from Nivå Bay species list, Zealand, Denmark. 7 records from Occurrence of mammalia relicts at site Tokod-Nagyberek. 2 records from Deep-water azooxanthellate Scleractinia from Vanuatu, and Wallis and Futuna Islands. 1203 records from Census of medical plant species of Benin (West Africa) by SOS Biodiversity. 10 records from Four new species of the subgenus Pachylaelaps (Longipachylaelaps) from Italy, with a new identification key to the known species (Acari: Pachylaelapidae). 12 records from BIRDRACE Vogelscheuchen. 58 records from Données opportunistes produites par Alexandre RUFFONI dans le cadre de l’élaboration d’un guide de détermination des larves de plécoptères. 5 records from First record of the millipede genus Nesorthomorpha Jeekel, 1980 in Vietnam with description of a new species (Diplopoda, Polydesmida, Paradoxosomatidae). 13 records from Birdrace-Die_Ornithomaten-Herford. 27 records from Two new day-flying species of Agrotis Ochsenheimer (Lepidoptera: Noctuidae) from the alpine summit of the Maunakea Volcano. 10604 records from Suivi Temporel des Rhopalocères de France (STERF). 148 records from Monitoreo de aves por medio de puntos de conteo en el Santuario de Flora y Fauna Galeras en 2018. 5 records from Genus Oribatula S. Str. Berlese, 1896 (Oribatida, Oribatulidae) In Romanian Fauna. 27 records from Fossil specimens in the Museum of Nature and Human Activities, Hyogo Prefecture, Japan. 35 records from Mammals (UWEP-MM). 5 records from Microbial diversity in shallow water hydrothermal sediments of Gueishan Island, Taiwan. 31 records from A new species of Coleophora (Lepidoptera: Coleophoridae: Coleophorinae) from the Galápagos Islands, Ecuador. 6 records from Landwehrbach. 54 records from On the systematic status of Isopericlimenaeus Marin, 2012 and its type species, Periclimenaeus gorgonidarum (Balss, 1913) (Crustacea: Decapoda Palaemonidae). 49 records from Revision of freshwater shrimps belonging to Caridina weberi complex (Crustacea: Decapoda: Atyidae) from Polynesia with discussion on their biogeography. 39 records from CSIRO, fish surveys by the Soela, 1980s. 10 records from Herpetofauna de la expedición Piedemonte Llanero - Proyecto Boyacá BIO UPTC. 2 records from Bryophyte speciments of Toyota City Nature Sanctuari (TCNS).. 16 records from Artenvielfalt in der Kinderakademie im RFZ. 4 records from Alien Species in Poland - Plants. 8 records from Microfossil abundance of Hole 16-158. 408 records from Herbario virtual bosques secos de Colombia - Sección herbario TULV (INCIVA). 80 records from Trawl-survey data from the “expedition Hvar” in the Adriatic Sea (Mediterranean) collected in 1948-1949. 16 records from Données de VINCENT Alexis (SAPROX). 170 records from Evaluación del riesgo de extinción de setenta y tres especies de lagartijas (Sauria) incluidas en la Norma Oficial Mexicana-059-SEMARNAT-2001. 3581 records from Vascular Plant Specimens of Yamagata Prefectural Museum. 16 records from Avifauna de bosques nublados en la cordillera Occidental, departamentos del Valle del Cauca, Risaralda y sur de Antioquia.. 307 records from Glasgow Museums BRC: Chrysomelidae. 3 records from A new species-group with new species of the genus Lasioseius (Acari: Mesostigmata: Blattisociidae) associated with Neotropical hispine beetles in furled leaves ofHeliconia. 6 records from Contribution to the taxonomy of the paper wasp genus Polistes (Polistella) (Hymenoptera: Vespidae: Polistinae) from Vietnam, with description of a new species. 1 records from Zetes pallidulus. 15 records from Données de la structure Forêts en Aulnoye provenant de la base de donnée du SINP Île-de-France CETTIA. 65 records from Taxonomic notes on the Polistes stigma group (Hymenoptera, Vespidae: Polistinae) from continental Southeast Asia, with descriptions of three new species and a key to species. 3 records from Soil bacterial diversity is associated with human population density in urban greenspaces. 3 records from Myriatrix. 2 records from The deep-water Calappidae, Matutidae and Leucosiidae of the Solomon Islands, with a description of a new species of Euclosia Galil, 2003 (Crustacea, Decapoda, Brachyura). 21 records from Two new species of the genus Laemostenus Bonelli sg. Antisphodrus Schaufuss from Turkey (Coleoptera: Carabidae: Sphodrini). 21 records from Taxonomic status of Macaronesian Eucyclops agiloides azorensis (Arthropoda: Crustacea: Copepoda) revisited - morphology suggests a Palearctic origin. 80 records from University Of Pretoria: Lacewing Database Project (1911-2015). 15 records from Freiheitsring (Frechen). 268 records from USAC Mammals Collection. 235 records from Données du naturaliste Doux Yves provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from Erythrodiplax ana sp. nov. (Odonata: Libellulidae) from Brazilian palm swamps. 266 records from Avifauna en dos parches de bosque seco del departamento del Valle Cauca (Colombia). 183 records from (Table 2) Mollusc biostratigraphy of facies underlying the 'Braunkohlensande' in the Lauenburg district, north Germany. 180 records from Données du naturaliste Christian Desmier. 203 records from Black flies (Diptera: Simuliidae) of Turkish Thrace, with a new record for Turkey. 3134 records from The collection of Bathynellacea specimens of MNCN (CSIC) Madrid: microscope slices and DNA extracts. 292 records from Fossil Specimens of Komatsu City Museum. 133 records from Odoanta of Akwa Ibom State University, Nigeria. 322 records from Pollen analysis of sediment profile KAIX_A from Kaiserwinkel. 44 records from Occurrence of mammalia relicts at site Geißenklösterle. 5 records from On the identity of Sternosternus grouvellei Guillebeau, 1894 (Coleoptera: Hydrophilidae, Phalacridae). 16 records from Taxonomic review of the genus Wasmannia.. 193 records from Diversidad y conservación del germoplasma de henequén Agave fourcroydes Lem. y su posible ancestro silvestre Agave angustifolia Haw.. 805 records from Données naturalistes de Bernard Lalanne-Cassou. 12101 records from Données naturalistes de Franck NOEL. 120 records from PSUZC-Reptile Collection. 8 records from Fauna de coleópteros lamelicornios del Estado de Michoacán. Primera Fase: Subprovincia neovolcánica tarasca (Cuenca del Lago de Pátzcuaro) 1995-96. 381 records from Données de collection de l'inventaire des Papillons de jour de Martinique. 129 records from Natura 2000 ZPS Jarny - Mars-la-Tour. 3 records from A new species of Oncopeltus Stål, 1868 (Heteroptera: Lygaeidae) in the nominate subgenus from Ecuador. 220 records from Avifauna asociada a paisajes rurales degradados en la vereda San Luis, Barrancabermeja - Santander. 7 records from Studies on the genus Aeolothrips (Thysanoptera: Aeolothripidae) in Iran, with a key to species. 8 records from The cavernicolous Oniscidea (Crustacea: Isopoda) of Portugal. 42 records from Fungal Bioblitz in Białowieża Primeval Forest at 18th Congress of European Mycologists. 180 records from Revisión de la subfamilia Asopinae (Hemiptera-Heteroptera-Pentatomidae) para México. 636 records from Données naturalistes de Matthias COLIN. 76 records from Appendix A: Results of the pollen analysis of the PG1755 core from Lake Billyakh. 2905 records from Colección general del plantas vasculares del Herbario JBB. 10 records from Review of the Pulvinaria (Hemiptera: Coccomorpha: Coccidae) species of the Ryukyu Islands, Japan. 9799 records from Colección de Entomología del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-E). 29189 records from Species data for Scottish waters held and managed by Scottish Natural Heritage, derived from benthic surveys 1993 to 2018. 703 records from Cowan Tetrapod Collection - Herpetology. 81415 records from CSIC-Real Jardín Botánico-Colección de Plantas Vasculares (MA). 1927 records from SPC NECTALIS Zooplankton/Micronekton specimens, New Caledonia 2014. 1 records from A contribution to taxonomy of the superfamily Grylloidea Laicharting from Yunnan, China (Orthoptera: Grylloidea). 100 records from Upper Silesian Museum, Bird Collection. 2275 records from DFO Pacific Groundfish Synoptic Trawl Surveys - Hecate Strait. 23498 records from Royal Belgian Institute of Natural Sciences Mammal collection. 15 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/049-3. 3774 records from CASES2003_2004. 4 records from Registros de mamíferos de los Parques Ecológicos Distritales de Montaña de Bogotá, D.C.. 11 records from Description of a new species of Loxosceles Heineken & Lowe (Araneae, Sicariidae) recluse spiders from Hidalgo, Mexico, under integrative taxonomy: morphological and DNA barcoding data (CO 1 + ITS 2). 65 records from Digitalización y sistematización de las colecciones biológicas del INECOL (Xiloteca). 2 records from Nouvelles fourmis de Madagascar.. 8 records from Hemmerder Schelk (Unna). 108 records from Shellfish (MNHM-MS). 10024 records from Fife Nature Records Centre combined dataset. 4 records from First records of 31 species of butterflies and moths (Lepidoptera) in Cameroon, with remarks on their elevational ranges. 2 records from Two new species of the spider genus Pholcus Walckenaer, 1805 (Araneae, Pholcidae) from Tajikistan, with the first description of female Pholcus sidorenkoi Dunin, 1994. 13 records from CHAS Botany Collection (Arctos). 20 records from New records of species of the Polyonyx sinensis group (Crustacea: Decapoda: Anomura: Porcellanidae) from Japan, the Philippines, Singapore, and Malaysia, with descriptions of two new species. 29 records from Avifauna asociada a humedales urbanos del municipio de Quibdó - Chocó, 2019. 183 records from Institut Botanic de Barcelona (IBB-CSIC-ICUB), BC-Lichen. 47 records from Refining the genus Rochinia A. Milne-Edwards, 1875: reinstatement of Scyramathia A. Milne-Edwards, 1880 and Anamathia Smith, 1885, and a new genus for Amathia crassa A. Milne-Edwards, 1879, with notes on its ontogeny (Crustacea: Brachyura: Epialtidae). 267 records from Hyperbenthos community in the salt marsh of Saeftinghe in 1990 and 1991. 287 records from Diagnóstico del aprovechamiento de flora y fauna por los mayas del Ejido Petcacab y evaluación de la cacería y pesca, Felipe Carrillo Puerto, Quintana Roo. 6 records from jamaica_invasive_alien_species. 2 records from Visual Plants (144.41.33.158) - Private collection of Florian Werner. 19 records from Naturschutzgebiet Lochbusch-Königswiesen. 708 records from Dragonfly biodiversity 90 years ago in an Alpine region: The Odonata historical collection of the MUSE (Trento, Italy). 22 records from Programme de valorisation des zones humides chassées - volet Oiseaux. 14 records from Rare species of animals and plants of the flood zone of the Oleksandrivka Reservoir of the Buzk's Gard National Nature Park. 1003 records from Odonata de Veracruz. 26 records from BIRDRACE Niederlausitz-Team. 1771 records from Cnidaria. 22 records from Chapter 7: Linnaean Plant Names and their Types (part T). 171 records from Revisions to the faunas of Andrena of the Iberian Peninsula and Morocco with the descriptions of four new species (Hymenoptera: Andrenidae). 2 records from A revision of the genus Boroecia Poulsen 1973 (Ostracoda, Halocypridae) with the descriptions of three new species. 37 records from Schulgarten Huttenheim (Philippsburg/Baden). 40 records from Línea base del medio biótico en los bosques dentro de la zona propuesta para Acuerdos de Conservación Voluntaria en la microcuenca de la Quebrada Aguazula - Rincón del Soldado_Yopal. 2149 records from Plant (JNHM-PL). 116 records from Inventaire et suivi Avifaune. 1222 records from Botanic Garden of the Finnish Museum of Natural History. 199 records from Poissons et Crustacés d'eau douce de la Martinique. 42 records from Two new species of Tipula (Vestiplex) Bezzi (Diptera, Tipulidae) from Northwest China. 4340 records from British Antarctic (Terra Nova) Expedition, 1910-1913. 167 records from The Masao Oita Insect Collection of The University Museum, The University of Tokyo. 7105 records from Invasive species - Chinese mitten crab (Eriocheir sinensis) in Flanders, Belgium. 15 records from A new species of Isoperla (Plecoptera: Perlodidae) from the Qinling Mountains of northwestern China and notes on the Chinese species of the genus. 3462 records from LACM Invertebrate Paleontology. 3 records from NZCS Kabo Studies 1989/1997/2011/2012. 1 records from Ice Wedge Polygon. 39 records from WildesMoor bei Schwabstedt. 234 records from The Paleontological Collections at the Bayerische Staatssammlung für Paläontologie und Geologie. 36 records from Diatom abundance measured on water bottle samples at station PS58/046-3. 75 records from Museums-Birds-Biodiversity-Records. 52 records from Deep-sea megabenthos of the Eurasian Central Arctic based on image analysis.. 5940 records from ZooplanktonBeaufortSeaNOGAP2. 25 records from More than just the number of denticles: morphometric and limb variability in Neotropical cladoceran Alonella dadayi (Crustacea: Cladocera: Chydoridae). 955 records from Sinfonevada: Dataset of Floristic diversity in Sierra Nevada forest (SE Spain). 20 records from Données des naturalistes POHIER et LEFORT provenant de la base de donnée du SINP Île-de-France CETTIA. 3641 records from CPAP - Herbário CPAP. 41 records from Biodiversity mapping in connection with Nature in Norway (NIN) in Vestland, Troms and Finnmark, Norway (2019). 389 records from Hermit crabs of the family Parapaguridae (Crustacea: Decapoda: Anomura) from Australia: species of Strobopagurus Lemaitre, 1989, Sympagurus Smith, 1883 and two new genera.. 21 records from Briófitos del cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO 2017. 20 records from CNMA/Colección de Mamíferos de la Estación de Biología Chamela. 1039 records from Central Siberian Botanical Garden Herbarium (NS, NSK). 1340 records from EAFM - Herbário do Instituto Federal de Educação, Ciência e Tecnologia do Amazonas. 221 records from Aves de fragmentos de Bosque seco en la región del Caribe Colombiano. 24 records from Rare species of plants in the southern part of the Sinyukha river basin. 2958 records from Los crustáceos decápodos marinos: Actualización de la colección carcinológica de la Facultad de Ciencias Biológicas, UANL. 5 records from Morphological description and DNA barcodes of adult males of Tanytarsus heliomesonyctios Langton, 1999 (Diptera, Chironomidae) in northeast of Russia. 1 records from Données naturalistes de Guillaume CHICA. 122 records from Registros del inventario y monitoreo de la Biodiversidad en la Jurisdicción de la Corporación Autónoma Regional de Cundinamarca CAR. 153 records from Jardín Botánico Atlántico, Gijón: JBAG. 45 records from Données de la naturaliste Marie Melun. 36 records from Données du naturaliste MARCHAL Olivier provenant de la base de donnée du SINP Île-de-France CETTIA. 87 records from étude entomologique de la ZSC du Bois de Vaires. 300 records from Données rhopalocères collectées par le CEN Aquitaine entre 1970 et 2015. 2 records from A new species of freshwater crab of the genus Strengeriana Pretzmann, 1971, from El Jardín Natural Reserve, Quindío, Colombia (Crustacea: Decapoda: Pseudothelphusidae). 66 records from DREAL_PACA_-_N2000_-_GIP_Calanques_2017_12_18. 11203 records from Estonian University of Life Sciences Institute of Agricultural and Environmental Sciences Vascular Plant Herbarium. 1740 records from Nearctic Anthomyzidae: a monograph of Anthomyza and allied genera (Diptera). 2 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Taynish Woods SSSI. 5 records from Baselines Initiative 16S rRNA gene dataset: Baselines Amplicon Release 1 (R1) Caribbean Sea near Curacao (including saline pond samples in Curacao) 2015. 12 records from Five new species of the spider genus Pholcus Walckenaer, 1805 (Araneae: Pholcidae) from China and Thailand. 24 records from Biotop Binsenwiesen und Ernst-Reiter-Wiese (Wehrheim/Taunus). 3 records from Two new species of the Simulium (Simulium) tuberosum species-group (Diptera: Simuliidae) from Palawan, the Philippines. 559 records from Kherson State University herbarium (KHER), Department of Botany. 2540 records from Colección de Herpetología del Instituto de Ciencias Naturales (ICN-MHN-Her). 4 records from "Schlechteberg" Ebersbach/Sa.. 25 records from Phytoseiid mites (Acari: Phytoseiidae) associated with tropical ornamental plants, with a checklist and a key to the species of Bahia, Brazil. 87 records from Medicinal potential of African plants (Togo). 380 records from Inventaire des Coléoptères Longicornes des Antilles françaises. 758 records from Nijmegen Natural History Museum (NL) - Herbarium. 1 records from 2019_nsmk_smpl_ms_20200603. 3 records from Two new species of amphipods (Crustacea: Amphipoda: Photidae) from Korean waters with a redescription of Gammaropsis longipropodi. 264 records from Checklist of decapod crustaceans from the coast of the São Paulo state (Brazil) supported by integrative molecular and morphological data: IV. Infraorder Anomura: Superfamilies Chirostyloidea, Galatheoidea, Hippoidea and Paguroidea. 751 records from Programme ACT : Répartition Pie bavarde 2007 - 2011 Coordonnées GPS Lambert 93. 13 records from Notes on types of Australian Chartocerus Motschulsky (Hymenoptera: Signiphoridae). 154256 records from Estonian Naturalists’ Society. 425825 records from Suffolk Biodiversity Information Service (SBIS) Dataset. 3 records from The Cainozoic to present-day record of Circum-Mediterranean, NE Atlantic and North Sea Cantharidinae and Trochinae (Trochoidea, Gastropoda) - a synopsis. 19 records from DEEPEND: Microbiome and bacterioplankton rRNA gene sequence data collected from Gulf of Mexico seawater samples. Cruises DP03 and DP04 from Jan 2016 - December 2016. 35 records from Les aires de plus grand intérêt patrimonial pour les ptéridophytes dans l'étage des forêts sempervirentes saisonnières tropicales à la Martinique. 2 records from MfN - Fossil invertebrates IIa. 14 records from Données rhopalocères 2014/2015 des Mattes de Paladon. 2 records from A new species of Metatanais Shiino, 1952 (Crustacea, Tanaidacea, Paratanaoidea) from Australian coral reefs, with a redefinition of the genus. 6 records from A Synopsis of the Odonata (Dragonflies) of Sumatra. 211 records from Département_du_Var_2017_12_18. 2 records from Occurrence of mammalia relicts at site Salzgitter-Lebenstedt. 221572 records from Carabidae records for Britain to 2014. 9 records from Polycentropus dinkinsorum (Trichoptera: Polycentropodidae), a newly described caddisfly species from the southern Appalachian Mountains, USA. 52 records from BARTH-Environnement_2017_12_18. 8463 records from CSIRO, Tropical Zooplankton Biomass and Composition, Albatross Bay - Gulf of Carpentaria, North Australia 1986-1988. 4 records from A checklist of Leiodidae (Coleoptera: Staphylinoidea) of Iran. 85 records from Dermaptera in the icipe collection. 92 records from Study of epibenthos and demersal fish in and around the thiocarbamate discharge area of the Belgian Continental Shelf (1977-1981). 7 records from SNH Invertebrate Site Condition Monitoring 2013/14: Dollar Glen SSSI. 987 records from SANBI: DNA Banking(1987-2011). 12872 records from The national database for marine data (MADS). 10 records from Phytoseiid mites of Slovenia (Acari: Mesostigmata): new records and first description of the male ofAmblyseius microorientalis. 20800 records from Naturalis Biodiversity Center (NL) - Mammalia. 9 records from New State Records Of Kentucky (Usa) Stoneflies (Plecoptera). 346 records from Colección de Entomología - Hymenoptera - Chalcidoidea. 1 records from New collections of freshwater crabs from northern Madagascar, with the description of a new species of Foza Reed & Cumberlidge, 2006 (Brachyura, Potamonautidae), and comments on their conservation status. 1 records from A new Limnonectes (Anura: Dicroglossidae) from southern Laos. 138 records from An annotated type catalogue of the centipedes (Myriapoda: Chilopoda) held in the Zoological Museum Hamburg. 168 records from Ghent university - Zoology Museum - Nematod Collection. 14 records from Swedish Malaise Trap Project (SMTP) - Syrphidae. 12 records from BIRDRACE Enger am Spektiv. 7 records from Sciapodinae from the Himalayan region with description of nine new species from Tibet (Diptera: Dolichopodidae). 1024 records from Données naturalistes de Julien BIRARD [Inventaire Eclair 18 juin]. 1 records from Données naturalistes de CLERGET sylvie. 3 records from Warnowufer Groß Klein. 2 records from Stadtrandlandschaft Apolda-Nord. 27 records from A checklist of amphibians at Lubuk Semilang Recreational Park, Langkawi Island, Kedah, Peninsular Malaysia. 169 records from Annotated checklist of the Hemiptera Heteroptera of the Site of Community Importance and Special Area of Conservation “ Alpi Marittime ” (NW Italy). 7566 records from Meetnetten.be - Population counts for dragonflies in Flanders, Belgium. 2 records from Tejidos de los ejemplares colectados en la expedición al municipio de San Francisco, Cundinamarca - Caracterizaciones Humboldt. 6 records from Echinoderms occurence in a strongly contaminated Bay (Portman, Spain), using ROV and Scuba-diving surveys. 1627 records from CSLA - Cal State LA Herbarium. 3 records from A new species of Alpheus Fabricius, 1798 (Decapoda: Caridea: Alpheidae) from the Caribbean coast of Panama. 3063 records from Sistemática e historia natural de algunos anfibios y reptiles de México. 30 records from BOTU-Fungi - Herbário Irina Delanova Gemtchújnicov - Coleção de Fungos. 1328 records from Diversidad de ocho grupos de insecta (Odonata, Lycidae, Phengodidae, Lampyridae, Cantharidae, Cerambycidae, Syrphidae y Vespidae) en tres regiones con bosque tropical caducifolio en México. 260 records from Colección del Herbario de la Universidad de los Llanos. 16977 records from Alterra (NL) - Entomofauna inventory in peat swamps. 81 records from Museu de Ciències Naturals de Barcelona: MCNB-Malac. 32 records from Pollen data of trap CB4. 153 records from annex1. 4 records from A new species of Glyphocrangon (Crustacea, Decapoda, Caridea, Glyphocrangonidae) from the Austral Islands, French Polynesia. 343 records from Programme ACT : Répartition Caille des blés 2012 - 2016 Coordonnées GPS Lambert 93. 1 records from Nothrus bicarinatus. 29 records from Rare vascular plant species in North-West of Kostroma region, Russia. 19 records from Draubiotop Lavamünd. 124 records from Extracellular DNA marine sediment Targeted Locus (Loci). 83 records from FBIP: Establishment of a fully data-based and barcoded collection of mushroom pathogens for South Africa. 15 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-14. 110 records from Netzfluegler_Raw1. 27 records from Nineteen new species of Megaselia Rondani (Diptera, Phoridae) from Denmark. 28 records from "Schwarzwassertal" bei Pobershau. 7 records from marine metagenome Targeted Locus (Loci). 8144 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Diptera_Tipulidae_Palearctic. 2789 records from Plan de vertebrados de la Patagonia. 403 records from Springtales from lichen communities at Kollåsen in Norway. 8 records from Birdrace_TerraCamper-Münster. 274 records from Swedish Malaise Trap Project (SMTP) - Sepsidae. 9 records from Apoyo a las colecciones biológicas de la Facultad de Ciencias de la UNAM: Fase 1 (FCME_AL). 39 records from AlgaTerra. 1601 records from LTB AVH data. 146 records from Records from the South Australian Seed Conservation Centre. 45020 records from Données acquises dans le cadre de l'activité du bureau d'étude BIOTOPE (1994 - 2013). 182 records from Danielsberg (Mölltal, Kärnten). 221 records from MfN - Fossil vertebrates III. 5 records from Vegetación vascular terrestre, entomofauna y macrofauna de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 8202 records from LPO_PACA_2017_12_18. 1 records from Abundance and community structure of birds breeding in Kalahari woodland used as rangeland. 18 records from Living Prairie Museum Manitoba Herbarium (LPMMBH). 29244 records from Oklahoma Vascular Plants Database Provider. 53 records from The Elachistidae (Lepidoptera: Gelechioidea) of Caucasus, with description of three new species. 30 records from Jasus caverum (Crustacea: Decapoda: Palinuridae) from the eastern South Pacific Ocean. 10 records from Borkhart. 1311 records from HSU Vertebrate Museum Mammals Collection. 22 records from Moniliophyta del Herbario BAB (Instituto de Recursos Biológicos CIRN-INTA). 209 records from Targeting a portion of central European spider diversity for permanent preservation. 1879 records from Liste des pays par taxon spécimen TOGO. 1584 records from Census of species recorded during phytosociological surveys in Benin. 916 records from 2019_NSMK_PL_2. 724 records from Programme ACT : Répartition Faisan commun 2009 - 2013 Coordonnées GPS Lambert 93. 58 records from NRW Regional Data: all taxa (sensitive species only), West Wales. 737 records from Foreign plant germplasm collections in Ghana. 409 records from 成龍溼地魚類生態紀錄. 36 records from List of Macroinvertebrate Species recorded in Vava’u during BioRAP survey. 102 records from Pollen analysis of sediment profile KAI2 from Kaiserwinkel. 70 records from Computarización de la Colección de mamíferos del Centro de Investigaciones Biológicas del Noroeste SC. 11 records from Informatisation des carnets de terrain de Georges Catherine. 4 records from New records of Panchaetothripinae from Japan (Thysanoptera, Thripidae). 15843 records from Acoustic monitoring data of avian species inside and outside the evacuation zone of the Fukushima Daiichi power plant accident. 4 records from Fauna Species of Camiguin Island, Philippines. 7 records from Fauna acuática asociada al Humedal Costero Obregón, Guapi, Cauca - 2013. 12 records from SNH Invertebrate Site Condition Monitoring 2015: Lurgie Loch SSSI. 11 records from Haplomunnidae (Crustacea: Isopoda) reviewed, with a description of an intact specimen of Thylakogaster Wilson & Hessler, 1974. 2 records from Monitoreo de mastofauna en corredores biológicos de Chiapas. 11409 records from UTEP Insects (Arctos). 8 records from Occurrence of mammalia relicts at site Bivak Cave. 15 records from Visual Plants (144.41.33.158) - Plants from Southern Ecuador; Ulf Soltau. 66 records from GNOR-Projekt "Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert" und Umland. 1076 records from Leicestershire Bryophyte Data. 9 records from Collection Pisces SMF. 78 records from Coral Reef Evaluation and Monitoring Project Dry Tortugas 2016. 4499 records from Staffordshire Wildlife Trust Nature Reserves Inventory. 4224 records from Herbarium specimens of Jardins botaniques and Conservatoire Botanique of Nancy (NCY). 3 records from Chandeleur Island 2016 Amplicon Study Raw sequence reads. 66 records from Microbial biogeography of 925 geothermal springs in New Zealand. 145 records from Banco de Germoplama del Jardín Botánico de Castilla-La Mancha. 21 records from Schulgarten Waldorfschule Hassfurt. 183 records from Vertebrados registrados durante el muestreo de tigrillos melánicos en el Valle del Cauca. 2060 records from Staatliches Museum für Naturkunde Stuttgart, Herbarium. 13 records from Wildlife Observations Bardon Hill 31.5.09. 11 records from http://www.geo-artenvielfalt.de (www.geo-artenvielfalt.de) - Birdrace-Pody&Co.-Plön. 121 records from Aquatic Insects from the Caatinga: checklists and diversity assessments of Ubajara (Ceará State) and Sete Cidades (Piauí State) National Parks, Northeastern Brazil. 53 records from Phenological Center - Mushrooms (Laplandskiy). 82 records from Revision of the squat lobsters of the genus Leiogalathea Baba, 1969 (Crustacea, Decapoda, Munidopsidae) with the description of 15 new species. 2919 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Entomology National Collection (MACNEn). 3 records from Middle Permian (Roadian) gastropods from the Khao Khad Formation, Central Thailand: Implications for palaeogeography of the Indochina Terrane. 2 records from A new deep-sea Cirripedia of the genus Heteralepas from the northeastern Atlantic. 99 records from Kieppi bird collection. 1 records from Arthropoden aus südostalpinen Höhlen.. 1 records from permafrost metagenome Targeted loci environmental. 4882 records from University of Alberta Vascular Plant Herbarium (ALTA-VP). 1069 records from Inventario de los ropaloceros (Lepidoptera) de la Sierra Gorda, estado de Querétaro, México. 5 records from Notes on the Carpophilus Stephens (Coleoptera: Nitidulidae) of Australia, with a new species from Victoria. 132 records from Revision of Chondrocyclus s. l. (Mollusca: Cyclophoridae), with description of a new genus and twelve new species. 4 records from New species and new records of Uropodina from Virginia, USA (Acari: Mesostigmata). 109 records from Eusocial wasp fauna of Sulawesi Island, the central island of Wallacea (Hymenoptera: Vespidae; Polistinae, Vespinae). 4 records from Specimens of Class Maxillopoda of Akita Prefectural Museum. 128 records from Plant specimens of the Museum of Yamagata University. 5 records from SNH Invertebrate Site Condition Monitoring 2015: Rinns of Islay SSSI. 3659 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Vascular Plants National Collection (BAv). 9735 records from CeDoc de Biodiversitat Vegetal: BCN-Cormophyta. 86 records from A first checklist of the Pteridophytes of Togo (West Africa). 124 records from Annales de la Société entomologique de France [1832- ]. 3 records from A new flower bug of the genus Montandoniola (Hemiptera: Heteroptera: Anthocoridae), a predator of gall-forming thrips on black pepper in southern India. 2 records from "Biodiversidad en el valle de Cuatro Ciénegas". (Ácaros acuáticos). 7 records from Type specimens in the Port Elizabeth Museum, South Africa, including the historically important Albany Museum collection. Part 2: Reptiles (Squamata). 27 records from Plantas de la expedición en el páramo de Rabanal, Boyacá - Proyecto Boyacá BIO. 10319 records from Atlantic Reference Centre Museum of Canadian Atlantic Organisms - Invertebrates and Fishes Data. 61780 records from Hymenoptera specimen database of Kyushu University. 20 records from Seasonal fluctuation of Macropipus holsatus in front of the Belgian Coast between 1973 and 1981. 228 records from Macroinvertebrados y perifiton pertenecientes a cuatro regiones de Colombia. 54579 records from Finnish Floristic Database (Literature Sources). 163 records from The Myriapoda Collection of the National Museum of Nature and Science. 216 records from Données du/de la naturaliste MOULIN Nicolas provenant de la base de donnée du SINP Île-de-France CETTIA. 33942 records from Belgian Coccinellidae - Ladybird beetles in Belgium. 4091 records from Survey and monitoring records for Scottish Wildlife Trust reserves from reserve convenors and Trust volunteers - Verified data. 27 records from Kochertgraben II. 62 records from Records of otters from Site Condition Monitoring in Scotland 2011-2012. 1978 records from Amphibian specimens. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 50 records from Inventaire avifaune. 6476336 records from iNaturalist Research-grade Observations. 7 records from The Anagyrus (Hymenoptera: Encyrtidae) parasitoids of the obscure mealybug Pseudococcus viburni (Hemiptera: Pseudococcidae) in Spain, with description of a new species. 7 records from Cuxhaven Schlosspark, Klasse 5e- Amandus-Abendroth-Gymnasium. 1212 records from DBRC Reptile Records 1950 - 2015. 75 records from Climate Change Adaptation Research Program (CCARP) Database of Watering Requirements - Images. 58 records from Anfibios y reptiles de la desembocadura del caño Teracay en el río Tomo, Puerto Carreño, Vichada - Proyecto Colombia Bio. 3 records from А new species of Alona Baird, 1843 (Cladocera: Chydoridae) from the ancient Lake Ohrid. 4 records from Cirolana bambang, a distinctive new species of Cirolana Leach, 1818 (Crustacea: Isopoda: Cirolanidae) from Bitung, Indonesia. 93 records from Mongolian Plant (MMNH-PL). 29 records from A review species of the genus Ceroplastes (Hemiptera: Coccomorpha: Coccidae) in China. 1758 records from Appalachian State University, I. W. Carpenter, Jr. Herbarium. 18 records from Superórden Dictyoptera del Museo de Entomología de la Universidad del Valle (Cali, Colombia). 44 records from Données Racoon sur le territoire de la Guadeloupe. 138 records from Anfibios y Reptiles asociados a tres ventanas de la Orinoquia Colombiana - SULU I. 109 records from Données du naturaliste DUFRENE ERIC provenant de la base de donnée du SINP Île-de-France CETTIA. 6 records from Mittelriede Höhe Gliesmarode-Braunschweig. 9858 records from University of Tennessee Bryophyte Herbarium. 201 records from JOIw - Xiloteca Joinvillea. 2244 records from PINK - Dragonfly (Odonata) monitoring for the permanent surveillance of coastal areas in Flanders, Belgium. 26 records from Streuobstwiese Kattenhund (Schleswig). 59 records from Incidence of pests and viral disease on pepino (Solanum muricatum Ait.) in Kanagawa Prefecture, Japan. 2 records from Heterogeneity of methane seep microbiomes in the NE Pacific. 776 records from Paleobotany Specimens. 1648 records from Global diversity and distributions of symbiotic copepod crustaceans living on octocorallians. 2083 records from Censo de ardeidas invernantes y nidificantes de la Comunidad Autónoma del País Vasco. 29 records from Hainhoop - Tonkuhle - Bullenmoor (Arpke). 1784 records from Likona Invertebrates. 28 records from SuLaMa reptile survey 2013. 9 records from Flora presente en áreas degradadas por minería en Condoto - Chocó, 2012. 18 records from Flora polínica de las llanuras de Sonora, al sur de Hermosillo. 4 records from A new species and notes on unusual natural history of Cladochaeta Coquillett, 1900 (Diptera: Drosophilidae). 87 records from Caracterización de la fauna y flora presente en los predios propuestos para el plan de restauración del distrito de conservación de suelos del cañon de rio grande (DCS-CRG), en el municipio de Dagua. 11827 records from Dorset Sites of Nature Conservation Interest (SNCI) species records pre 2000. 2 records from VFD-H: MIttelgebirgsweide. 417 records from Programme ACT : Répartition Caille des blés 2006 - 2010 Coordonnées GPS Lambert 93. 11 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE218. 1116 records from Amphibiens de Guyane. 35 records from Anémonas y corales del atolón Albuquerque durante la Expedición Seaflower 2018 - Proyecto Colombia BIO. 11 records from Visdoorgangen - Fish passage places in Flanders, Belgium. 676 records from Colección de artrópodos del PNN Gorgona - Museo de Entomología de la Universidad del Valle (MUSENUV). 75 records from Liste d'espèces animales recensées au cours des activités de l'Organisation pour le Développement Durable et la Biodiversité (ODDB ONG) au Bénin. 23463 records from University of California Museum of Paleontology. 1 records from Two new species, including one representing a new genus, of the West African millipede family Campodesmidae (Diplopoda: Polydesmida). 2465 records from DBRC Hemiptera species records 1969 to 2015. 4 records from BB-Biodiversität a. 10 records from Collection Myriapoda - SNSD. 8987 records from Dreal Corse - Base Ogreva. 36 records from Lophogastrida and Mysida (Crustacea) of the “ DIVA- 1 ” deep-sea expedition to the Angola Basin (SE-Atlantic). 12 records from Censo de aves acuáticas nidificantes de la Comunidad Autónoma del País Vasco. 10064 records from Stackpole National Nature Reserve Species Inventory and Ad-hoc Sightings from Across Pembrokeshire. 28 records from A conspectus of the silver-flies (Diptera: Chamaemyiidae) of the Middle East with descriptions of new species of Chamaemyia Meigen and Melanochthiphila Frey, from the Arabian Peninsula. 539 records from Herbario de Plantas Vasculares de la Asociación BIGA para el estudio del patrimonio natural de Galicia: FBIGA. 27038 records from University of Tennessee Vascular Herbarium. 867 records from Dorset SW Pilot species dataset. 4 records from Rhopalocera of Martinique. 484 records from Herbario de Hongos de la Universidad de Salamanca: SALA-Fungi. 3497 records from Flora of the Stołowe Mts.. 668 records from Chronicle of Nature - Phenology of Insects of State Nature Reserve Olekminsky. 74 records from Données de la structure Philofauna provenant de la base de donnée du SINP Île-de-France CETTIA. 3 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 1 records from Two new species of Hydroptilidae (Insecta: Trichoptera) from the Serra dos Carajás, Pará state, northern Brazil. 135 records from MCCC - Mendocino College Coast Center Herbarium. 1497 records from Occurrence data of dragonflies available at the National Museums of Kenya's Natural History Collection, Invertebrates Zoology Section.. 3 records from A redescription and a synonym in the South Asian millipede genus Xenobolus Carl, 1919 (Spirobolida, Pachybolidae). 69150 records from Insect (KNAM-IN). 25 records from Macroinvertebrados acuáticos asociados a humedales urbanos del municipio de Quibdó - Chocó, 2019. 49 records from The genus Clubiona Latreille, 1904 (Araneae: Clubionidae) in the Maghreb, with notes on the genevensis group and new records from the Mediterranean Region. 107 records from Alien plants of Salavat. 10 records from BIRDRACE Bielefinken. 7 records from données arachnologiques de GUERBAA Karim. 8 records from Unraveling the species diversity and relationships in the Leptodactylus mystaceus complex (Anura: Leptodactylidae), with the description of three new Brazilian species. 489 records from Cumbria Non Native Invasive Species. 6483 records from FloVegSI - Floristical and fitocenological database of ZRC SAZU. 4 records from Inventaire et suivi de la faune écrasée. 21 records from Geographical and bathymetric distribution of mysids (Crustacea: Mysida) in the seas of the Iberian Peninsula. 185 records from Pollen profile from Seminary School Basin. 23042 records from Données photographiques validées de la galerie du forum "Le Monde des Insectes". 27145 records from Santa Barbara Museum of Natural History Entomology Collection. 23 records from Species occurring in the mytilid and alvinellid communities within the 9°N hydrothermal field at the East Pacific Rise. 3 records from Teretamon spelaeum, a new species of freshwater crab (Crustacea: Decapoda: Potamidae) from a limestone cave in Meghalaya, India. 36 records from BIRDRACE Gätkes Erben. 555 records from Benthos counted on dredged samples during Valdivia cruise VA53. 8 records from Ejemplares de Criptogamas de Chile en el Herbario CORD. 26985 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 7 records from Description Of A New Species Of Pterostichus Bonelli, P. barri, From The Appalachian Mountains (Coleoptera: Carabidae). 75 records from Axel W. Erikssons African Bird Collection at Vänersborg Museum. 1107 records from Carabidae of the European North-East of Russia. 391 records from Actualización y depuración de las bases de datos de la Colección Nacional de Helmintos: P085 y Q028. 15 records from BIRDRACE federleser. 807 records from Análisis de los efectos ecológicos del aprovechamiento forestal en el Corredor Biológico Mesoamericano: mamíferos, plantas y sus interacciones. 62 records from (Table 4) Ostracoda abundances in sediment core PS2212-3 (Yermak Plateau). 310 records from The Fishery Grounds near Alexandria.VII.Decapoda.By Heinrich Balss.(1936).Notes and memoirs No. 15. 6 records from Inventaire biodiversité du site Pierre Fabre de Gaillac. 48647 records from CAS Botany (BOT). 8 records from Otiorhynchus (Choilisanu s) theophrastus sp. nov. from Lesbos Island, Greece (Coleoptera, Curculionidae, Entiminae). 7 records from CCA_pathobiome. 226 records from Données naturalistes d'Anaïs MAS. 2 records from Microbial community diversity in Arctic marine sediments and Planktonic microbial. 17 records from Three New Species Of Aegla (Anomura) Freshwater Crabs From The Upper Uruguay River Hydrographic Basin In Brazil. 1 records from New records of family Hormathiidae (Cnidaria: Actiniaria) from Brazilian coast with description of Paraphelliactis labiata n. sp.. 6 records from Occurrence of mammalia relicts at site Stematia. 2 records from Dysdera dushengi sp. nov., the easternmost species of the spider family Dysderidae (Arachnida: Araneae). 9620 records from The Myriapoda & Onychophora collection (MY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 6 records from Données du/de la naturaliste Thibault Marie Thérèse provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from New data on the Syrphidae (Diptera) of Iran, with descriptions of two new species. 3 records from Rare myodocopid ostracods from Mesozoic sections of Hungary: summary, revision and description of new taxa. 394 records from Barents Sea Zooplankton – March and May 1998 and July 1999. Zooplankton sampling on board the Norwegian R/V Jan Mayen, program ALV. 353 records from Revision of the Nearctic genus Tritoxa Loew (Diptera: Ulidiidae). 8 records from uncultured eukaryote Raw sequence reads. 325 records from ARC-PPRI: National Collection of Nematodes and South African Plant-Parasitic Nematode Survey(1901-2014). 738 records from Arachnids (Aranei, Opiliones) from grass stand and forest litter in the Urals, Russia. 11 records from Ground spiders (Araneae: Gnaphosidae, Liocranidae, Prodidomidae) from the Greek islands Rodos, Symi and Karpathos, with the description of new species. 221 records from Relevé de collections de lépidoptères rhopalocères et de coléoptères saproxyliques.. 59 records from Bishop's University Insect Collection (BUIC). 39 records from Catalogue of the herbarium specimens collected from Discovery Bay and Runaway Bay, Jamaica, West Indies, 1958-1999.. 3 records from ALTERECO_2017_12_18. 3 records from Caracterización Ecológica de la Fauna del Páramo de Frontino o del Sol. 2250 records from MBON POLE TO POLE: SANDY BEACH BIODIVERSITY OF YUCATAN COAST. 92400 records from BioFokus. 2114 records from Anymals+plants - Citizen Science Data. 54 records from Chronicle of Nature - Phenology of Insects of FSBI Zeya State Nature Reserve. 8453 records from Arctic benthic invertebrate collection of the Zoological Institute of the Russian Academy of Science. 3449 records from Tartu University fossil collections. 27 records from MFS-Frutos - Herbário Profª. Drª. Marlene Freitas da Silva - Coleção de Frutos. 267 records from Occurrences of the Insects in the Prioksko-Terrasny biosphere reserve. 297 records from Données avifaune de Guadeloupe. 558 records from Données du/de la naturaliste CARON Julien provenant de la base de donnée du SINP Île-de-France CETTIA. 3 records from Submarine Ligurian Canyons Water Prokaryotic and Protist Communities. 8532 records from UMNH Reptiles and Amphibians Collection (Arctos). 7 records from Nonmarine Ostracoda (Crustacea) from Jeju Island, South Korea, including descriptions of two new species. 5155 records from Bryophyte specimens of National Museum of Nature and Science (TNS). 29 records from Fossil (WSHN-FO). 34 records from Plants, Bryophytes and Lichens recorded on the Nevis Estate during summer 2003.. 1 records from A new species of genus Nippononebria Uéno (Coleoptera, Carabidae, Nebriini) from Changbai Mountain, Jilin Province, China, the first species of the genus confirmed from the Asian mainland. 7 records from The fishes collection (IC) of the Muséum national d'Histoire naturelle (MNHN - Paris). 4 records from A new species of the genus Podothrips Hood- - (Thysanoptera; Phlaeothripid- - ae) from Thailand- -. 11 records from BIRDRACE Di-Bi-Di-Birder. 52 records from DBG Tissue and DNA Bank. 12 records from Three new species of Heteromysis (Crustacea: Mysida) from coral reef aquaria in Florida and Central Europe. 6 records from A new species of the genus Liljeborgia Spence Bate, 1862 (Crustacea: Amphipoda: Liljeborgiidae) associated with the burrows of the spoon worm Urechis unicinctus in the Sea of Japan. 13 records from Description of five new species of the genus Stigmaeus Koch (Acari: Raphignathoidea: Stigmaeidae) from Turkey. 2851 records from EDP Baixo Sabor: Land Birds - Construction and Reservoir Filling Phases: stream weirs in the Sabor tributaries [2010-2014]. 46 records from Collection de C.C.H. Jongkind aux Monts Nimba. 10 records from Données du/de la naturaliste Champagne Alain provenant de la base de donnée du SINP Île-de-France CETTIA. 31 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Aves Nidos (MFA-ZV-Or-N). 121 records from HerbarioHerrerense. 86 records from Database_Dragonflies_ Madagascar Biodiversity Center PBZT. 1016 records from Museu de Ciències Naturals de Barcelona: MCNB-Pal. 13 records from A revision of the subgenus Eurycercus (Teretifrons) Frey, 1975 (Crustacea: Cladocera) in the Holarctic with description of a new species from Russian Arctic. 142 records from Butterflies of Singapore and Peninsular Malaysia (Pieridae). 11081 records from CZE National PGR Inventory. 10 records from Occurrence of mammalia relicts at site Geyerloch. 202 records from Pollen profile Märchenwald B, Harz, Germany. 36 records from Microzooplankton abundance measured on water bottle samples at station PS58/048-3. 4 records from Mammalia (JNHM-MM). 358 records from Digital Atlas of Trees and Wildlife in Thailand. 2 records from A new species of the mud shrimp genus Axianassa Schmitt, 1924 (Decapoda Gebiidea: Laomediidae) from Japan. 3 records from Chirocephalus sanhadjaensis sp. nov., a new chirocephalid species (Branchiopoda: Anostraca) from Numidia (Algeria). 665 records from Macroinvertebrate abundance data from the littoral zone of a number of large New Zealand lakes. 252 records from SPC PROCFish/C Invertebrates Observations Solomon Islands 2006. 1 records from Biodiversidad de los Ecosistemas Mesofóticos de la Isla de San Andrés. 9 records from Additional notes on Psychotria (Rubiaceae) from the southern karst of Papua New Guinea: P. defretesiana comb. et stat. nov., P. dieniensis var. banakii var. nov., and P. stevedarwiniana sp. nov.. 2181 records from The Vascular Plants Collection of the University of Goettingen. 15634 records from Occurrences de vecteurs de maladies recensées à l'Hôpital de Mènontin. 519 records from Flora vascular acuática de la cuenca del Río Tamesí. 717 records from Programme ACT : Répartition Faisan commun 2008 - 2012 Coordonnées GPS Lambert 93. 332 records from Distribution of ostracoda in the Arctic Ocean (Table 1). 13 records from A new genus and two new species of miniature clingfishes from temperate southern Australia (Teleostei, Gobiesocidae). 5 records from Description of Alpheus gallicus, a new deep-water snapping shrimp from Galicia Bank, northeastern Atlantic (Malacostraca, Decapoda, Alpheidae). 7 records from Ice Amphipods Canada Basin. 43 records from flower availability 2008 Hainich. 1359 records from Royal Museum of Central Africa - Metafro-Infosys - Xylarium. 7 records from New contributions to the Eulophidae fauna from Morocco (Hymenoptera: Chalcidoidea) with comparison in the North African region. 21308 records from Base de datos de plantas vasculares del País Vasco: ARAN-EH. 891 records from Andes to Amazon Biodiversity Program. 624 records from Echigo-Matsunoyama Museum of Natural Science, Usuke Shiga butterfly collection. 62 records from Miljodir_naturtypekartlegging_2017. 20 records from Suivi botanique et entomologique pour la gestion de la portée de RTE sur l'emprise de la RNN de Bassée. 75 records from Inventario herpetofaunístico del noroeste de Hidalgo. 4415 records from EDP Foz-Tua: Macrophytes – Ecological Monitoring Program [2011-2015]. 113 records from nsmk_mm_2019. 124 records from SNH Invertebrate Site Condition Monitoring 2013/14: Cairngorms SSSI. 9 records from Morphological and molecular analyses confirm the occurrence of two sympatric Lysmata shrimp (Crustacea, Decapoda) in the southwestern Atlantic. 33 records from Chronicle of Nature - Phenology of Arachnids of Visimsky Nature Biosphere Reserve. 4 records from Caracterización de Flora de la Reserva Forestal Protectora Regional Brisas del Rincón. 15 records from Description of a new species of Caridina (Crustacea: Decapoda: Atyidae) from two Micronesian islands (Guam and Babeldaob). 5 records from Mollusc collection Natuurmuseum Brabant, Tilburg. 706 records from Vegetation of Rybachy Peninsula and Srendny Peninsula, Murmansk Oblast, Russia. 42 records from Rund um den Eichwald,Schulhof Friedrich Fröbel Gymnasium- Bad Blankenburg. 12 records from Données espèces - Expertise IPE 15. 7 records from Phytoplankton abundance measured on water bottle samples at station PS65/470-1. 520 records from DAR AVH data. 9 records from ISTOTA - Schulgarten in Krakau, Stadtteil Ludwinow. 581 records from Données naturalistes de Jérôme BARBUT. 35697 records from England Non Native Species records 1965 to 2017. 33 records from Diatom abundance measured on water bottle samples at station PS58/011-3. 145 records from Swedish Malaise Trap Project (SMTP) - Rogadinae. 61 records from Bird Collection of Otto Hedin. 2 records from The discovery of Euryrhynchidae (Crustacea: Decapoda) in India, with the description of a new genus and species. 2 records from Occurrence of mammalia relicts at site Bettenroder Berg IX. 9 records from L’évaluation environnementale du projet du barrage de la retenue d'eau, de Guinea Alumina corporation à sangaredi, Boké (CESP2016-022). 1 records from DBL_Life. 4 records from Multiple original spellings, living authors and the Code: The case of Malachius raniansis Mawlood, Hammamurad & Abdulla, 2017 (Coleoptera: Melyridae). 120 records from Reef Check in Taiwan 台灣珊瑚礁體檢. 3 records from Two new South American species of Monomorium Mayr with taxonomic notes on the genus.. 3 records from Validation of the ghost shrimp species Neocallichirus pinheiroi Hernáez, Windsor Paula & Santana (Decapoda: Callianassidae) from the southwestern Atlantic. 25 records from Thirteen new species of the spider genus Pholcus Walckenaer, 1805 (Araneae: Pholcidae) from China. 2 records from A new species of Simulium (Gomphostilbia) (Diptera: Simuliidae) from South India. 28835 records from CNS AVH data. 25 records from Colección Ornitológica de la Universidad Tecnológica del Chocó. 16 records from Pedestrian mammals census in W National Park. 186 records from PINK - Amphibia monitoring for the permanent surveillance of coastal areas in Flanders, Belgium. 1960 records from BLS Rare and Threatened Lichen Records: England. 4 records from New morphological information on Simulium wygodzinskyorum Coscarón & Py-Daniel, 1989 (Diptera: Simuliidae). 9 records from Coastal Marine Environment Targeted loci environmental. 43 records from Gronau - auf der Suche nach dem Neunauge. 79 records from Fungal diversity in Sanya mangrove sediments, China. 176 records from Programme national de science participative sur la Biodiversité Littorale (BioLit). 8543 records from Eden Arthropod Azores Database. 1128 records from Inventaire de la flore des Pyrénées-Atlantiques 2007-2008 - Littoral. 20 records from Lepidoptera from Rancho Grande, Rondônia, Brasil. 3 records from A new species of the hermit crab genus Diogenes Dana, 1851 (Decapoda: Anomura: Diogenidae) from southern India. 2 records from Faunal assemblage of sediment core GS7603-8. 1509 records from Thrips (Thysanoptera) in Norway. 7 records from Artsrike vegkanter i Haugesund. 60 records from Levantamento de Mamíferos do Parque Nacional da Quiçama - INBAC/RWCP - 2017. 3 records from A new species of Homo from the Late Pleistocene of the Philippines. 41 records from Pollen profile from sediment core AV14_K2-4. 17 records from Entdeckertour am Muldestausee 1/05. 662 records from Banco de Vida/ CJ Museum/ Amphibian collection. 13646 records from University of Colorado Museum of Natural History Herbarium Vascular Plant Collection. 2 records from Deux nouvelles espèces d’ Aloe L. (Xanthorrhoeaceae, Asphodelaceae), section Lomatophyllum Rowley, de Madagascar. 1442 records from Abundance and distribution of coastal, inshore zooplankton in the Huon Estuary and D'Entrecasteaux Channel, Tasmania, Australia (2004-2005). 17 records from Implementación de la bioindicación en el Río Cauca - 2016. 201 records from Mammalian Specimens of the Yamagata Prefectural Museum. 6 records from BID-Malawi-Arctiidae-Biodiversity-Data. 43 records from Antarctic and sub-Antarctic Lophogastrida occurrences. 251 records from Reptilia collection of the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 22 records from Bird specimens of Ryukyu University Museum (Fujukan). 1 records from pp 56 - 66, plates 1 - 4 in Monographie des Libellulidées d'Europe. 429 records from Chronicle of Nature - Phenology of Plants of State Environmental Institution National Park Braslav lakes. 1466 records from Inventaire de la flore du PNRLG 2016 (Gironde). 3 records from A new species of Mesochra (Copepoda: Harpacticoida: Canthocamptidae) from a coastal system of northern Colombia with a key to the American species. 33 records from New gnathiid isopod crustaceans (Cymothoida) from Heron Island and Wistari Reef, southern Great Barrier Reef. 461 records from Royal Belgian Institute of Natural Sciences marine Chelicerata collection. 2 records from Birdrace_Gätkes_Schergen-Helgoland. 37 records from Taxonomic review of Ablabesmyia Johannsen (Diptera: Chironomidae: Tanypodinae) from Oriental China, with descriptions of six new species. 35 records from CECT Spanish Type Culture Collection(Fungi). 2 records from Occurrence of mammalia relicts at site Crumstadt 1. 836541 records from Finnish Bird Ringing and Recovery Database. 22298 records from New Zealand Fungal and Plant Disease Collection (PDD). 4 records from Schulhof der Hermann-Runge-Gesamtschule (Moers). 26 records from New records of Munidopsis (Crustacea: Anomura: Galatheidae) from New Zealand with description of two new species from a seamount and underwater canyon. 41 records from Ecosystem biomonitoring with eDNA: metabarcoding across the tree of life in a tropical marine environment. 891 records from Mamíferos de Nuevo León: distribución y taxonomía. 38 records from Umgebung der Grundschule Oderberg. 6 records from The family Hyalidae (Crustacea: Amphipoda: Talitroidea) from Korean waters. 2. Genus Protohyale Bousfield & Hendrycks, 2002. 11 records from A new species of the Rhinella margaritifera (Laurenti 1768) species group (Anura Bufonidae) from southern Brazilian Amazonia. 56 records from Pollen analysis of sediment profile BLA00 from Blankensee. 74 records from Patrones de diversidad florística y faunística del área focal Ixcan, selva Lacandona, Chiapas (Plantas). 4 records from Données naturalistes d'Olivier VILLEPOUX. 431 records from Galathea II, Danish Deep Sea Expedition 1950-52. 499 records from Colección del Herbario de la Universidad Tecnológica del Chocó. 20 records from Endofauna abundance in 2006-10 from an experiment in the Wadden Sea of List, Sylt. 111 records from Aves de la cuenca media del río Chambery, Caldas. 12068 records from NCSM Non-molluscan Invertebrates Collection. 13004 records from The AAU Herbarium Database. 697 records from DSMZ Collection of Plant Viruses. 2 records from New and little-known species of Empis (Diptera: Empididae) from Bulgaria, Israel and Turkey, with keys to the Palaearctic Pachymeria and the Mediterranean Xanthempis. 4 records from New Antarctic stenothoids sensu lato (Amphipoda, Crustacea). 6 records from Three new species of the family Phytoseiidae (Acari: Mesostigmata) from Turkey. 535 records from Herbarium specimens of Institut Scientifique Mohamed V university (RAB). 1 records from Museu Paraense Emílio Goeldi - Mollusca Collection. 54 records from Sistematización de la Colección Entomológica Forestal del CENID-COMEF. 12130 records from BioGIS - Vascular plants - A. Danin's grid database. 28 records from Sixty new dragonfly and damselfly species from Africa (Odonata). 353 records from Bird Monitoring 2017, Meise Botanic Garden. 2651 records from Colecção Entomológica do Museu de História Natural de Maputo. 113 records from Herbier du Muséum Henri-Lecoq de Clermont-Ferrand - Rosacées. 2011 records from Inventario arbóreo del Jardín Botánico Universitario del campus Meléndez de la Universidad del Valle, Santiago de Cali.. 27 records from Microzooplankton abundance measured on water bottle samples at station PS58/042-2. 347 records from Epifitos vasculares y no vasculares en 7 remanentes de bosque seco tropical en el Valle del Cauca. 7 records from Oiseaux(Faune des mangroves et des zones humides du sud Togo). 301 records from Mirmecofauna de la reserva ecológica de San Felipe Bacalar. 92 records from Heritage Trees of Ireland. 2469 records from flower visitor interactions 2008. 44 records from Chronicle of Nature - Phenology of Birds of Volzhsko-Kamsky National Nature Biosphere Rezerve. 1 records from Three new species of Elachistidae (Lepidoptera: Gelechioidea) from India. 10 records from Craigellachie NNR invertebrate records compiled from SNH files. 2 records from Variation in freshwater stream sediment community 16S rRNA profiles along an urbanization gradient. 2 records from Labrumoides vibrissa (Arthropoda: Pycnogonida), new callipallenid genus and new species from north Western Australia. 3597 records from Gloucestershire Naturalists' Society Spider Records 1930 - 2013. 4 records from VFD-HH/SH: Pferdweide Lammert. 360 records from Données espèces - Expertise IQE 92. 12990 records from imr_mareano_rpsledge. 44 records from Données du/de la naturaliste LUPOLI ROLAND provenant de la base de donnée du SINP Île-de-France CETTIA. 7172 records from Herbario de la Facultad de Ciencias Biológicas de la Universidad Complutense de Madrid (MACB). 217 records from Mammal specimens of Saitama Museum of Natural History. 1037 records from Tetranychus urticae literature occurrences in a predator-prey system: Phytoseiulus persimilis (Acari: Phytoseiidae) and Tetranychus urticae (Acari: Tetranychidae). 16748 records from Plant Specimen from Herbarium (IBK) in China, Guangxi Institute of Botany, Chinese Academy of Sciences. 24 records from Mammals of Korea: a review of their taxonomy, distribution and conservation status. 10 records from A new species of Biffarius Manning & Felder, 1991 (Decapoda: Axiidea Callianassidae) from the intertidal coast of northeastern Brazil. 43 records from Occurrence database of bryophytes and native animals of southern Chile. 6 records from VFD-H: Heidenrod: Pferdeweide Mürth. 1531 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Entomologica San cristóbal). 44 records from Sangmi Lee Research Collection. 42 records from Revision of the terrestrial isopods of the subgenus Hemilepistus (Desertellio) Verhoeff, 1930 (Isopoda: Oniscidea). 108190 records from Larvae of decapods off Portuguese coast from 1986 to 1994. 38 records from Données 2015 de l'Observatoire de la Biodiversité des Forêts. 1212 records from California State University, Long Beach Mammals. 44 records from Tejidos de individuos colectados en el plan de monitoreo de biodiversidad en el bloque platanillo de la empresa Amerisur y en los bloques Rumiyaco, Venados y Burdyne de la empresa Gran Tierra, Putumayo. 3711 records from Données mammifères Midi-Pyrénées enregistrées dans BazNat - Lot 2. 1088 records from Ostracoda in sediment core PS51/154-11. 25 records from Nottekanal, Klasse 7 - 10. 30 records from Environmental long read amplicons of soil fungi across Podzol soil profile. 6833 records from données aranéologiques de CORNIC Jean-François. 29 records from Suivi de la flore patrimoniale de la RNR de Saint-Assise (77) dans le cadre d'un stage de M2. 103 records from Annotated checklist of the Dermaptera (Insecta) of French Guiana. 11 records from Données espèces - Expertise IPE 69. 8 records from Waldwiese. 12 records from A new species of Plestiodon (Squamata: Scincidae) from the Balsas Basin, Mexico. 8 records from (Table 1) Fauna composition of the community of Amphiodia urtica - Nephtys ferruginea in bottom sediments from the central part of the shelf in the California upwelling zone. 532 records from Clare Biological Records Centre Dataset 2004-2007. 29 records from Riqueza y distribución de briófitos reófilos en el predio Golconda, ubicado en el municipio de Hato, Santander. 323 records from Inventario florístico en Baja California Sur: Región del Cabo e Islas adyacentes. 2111 records from Universi
Keywords: GBIF; biodiversity; species occurrences